Seafloor troughs offshore southwestern Taiwan revealed by AUV and ROV observations - Tzu-Ting Chen; Charles K. Paull; Char-Shine Liu; Chih-Chieh Su; Ho-Han Hsu; Liang-Fu Lin; Dave W. Caress; Roberto Gwiazda; Eve Lundsten; Shao-Yung Liu; Ling-Ji Mu; Arif Mirza (Geomorphology, 2026)

Robot-assisted Neural Radiance fields for plot-level cotton crop 3D reconstruction and yield estimation - Lizhi Jiang; Peng W. Chee; Changying Li; Longsheng Fu (Computers and Electronics in Agriculture, 2026)

Tracking Cretaceous to present day deep-sea sedimentary hiatuses driven by intensified bottom-water currents - Jiewei Hu; Dengfeng Li; David Chew; Simon W. Poulton; Yanhui Dong; Jinzhou Peng; Yu Fu; Xiaoming Sun (Earth and Planetary Science Letters, 2026)

Corrigendum to “Seafloor troughs offshore southwestern Taiwan revealed by AUV and ROV observations” [Geomorphology 512 (2026) 110490] - Tzu-Ting Chen; Charles K. Paull; Char-Shine Liu; Chih-Chieh Su; Ho-Han Hsu; Liang-Fu Lin; David W. Caress; Roberto Gwiazda; Eve Lundsten; Shao-Yung Liu; Ling-Ji Mu; Arif Mirza (Geomorphology, 2026)

Organic matter controls rare earth element hyper-enrichment in Pacific deep-sea bioapatite - Xijiao Liao; Dengfeng Li; Simon W. Poulton; John R. Reinfelder; David Chew; Yu Fu; Yongjia Liang; Zhengkun Li; Jinzhou Peng; Xiaoming Sun (Geochimica et Cosmochimica Acta, 2026)

Precision measurement of the Ds*+-Ds+ meson mass difference - M. Ablikim; M.N. Achasov; P. Adlarson; X.C. Ai; R. Aliberti; A. Amoroso; Q. An; Y. Bai; O. Bakina; Y. Ban; H.-R. Bao; V. Batozskaya; et al. (Science Bulletin, 2026)

Forward dynamic programming-informed Bayesian method for optimal power allocation in short-sea shipping - Daniel Vergara; Shanshan Fu; Wengang Mao; Jonas W. Ringsberg; Tsoulakos Nikolaos (Ocean Engineering, 2026)

Contrasting behaviour in geogenic degassing along an active segment of the East Anatolian fault zone (Türkiye) - G. Yüce; W. D'Alessandro; C.C. Fu; F. Italiano; M. İçhedef; H. Elmacı; B. Kürkcüoğlu; B. Kahraman; A. Demirtaş; L.H. Lin; D. Yasin; Ş. Gürboğa; et al. (Applied Geochemistry, 2026)

Correction: Metagenomics reveals diverse community of putative mercury methylators across different biogeochemical niches in Sansha Yongle blue hole - Heyu Lin; Xiao-Yu Zhu; Chun-Xu Xue; Peng Yao; Liang Fu; Zuosheng Yang; Xiao-Hua Zhang; John W. Moreau (Marine Life Science & Technology, 2026)

Paracremonium yunnanense (Sordariomycetes), a New Fungus From Swallow Cave in Yunnan Province, China - Xiang‐Fu Liu; Saowaluck Tibpromma; Kevin D. Hyde; Jayarama D. Bhat; Dong‐Qin Dai; Abdallah M. Elgorban; K. W. Thilini Chethana; Samantha C. Karunarathna (New Zealand Journal of Botany, 2026)
In this article, we describe a new cave‐associated fungus belonging to Nectriaceae (Hypocreales), collected from the air in Swallow Cave, Yunnan Province, China. Initial morphological observations confirmed that our collection exhibits characteristics typical of an acremonium‐like species. Phylogenetic analyses of the combined internal transcribed spacer (ITS), large subunit ribosomal RNA (LSU), and β‐tubulin ( TUB ) sequence dataset confirmed that our fungus forms an independent lineage within Paracremonium , sister to P. bendijkiorum , P. apiculatum , and P. variiforme . Based on morphology and multigene phylogeny, we describe our fungus as a new species, Paracremonium yunnanense . A comprehensive description, micrographs, and a phylogenetic tree showing the placement of the new species are provided. Moreover, our results contribute to understanding the genus Paracremonium and expand the knowledge of cave‐associated fungi in China.

First evidence of CP violation in beauty baryon to charmonium decays - R. Aaij; A.S.W. Abdelmotteleb; C. Abellan Beteta; F. Abudinén; T. Ackernley; A.A. Adefisoye; B. Adeva; M. Adinolfi; P. Adlarson; C. Agapopoulou; C.A. Aidala; Z. Ajaltouni; et al. (Science Bulletin, 2026)

Biochar reshapes soil bacterial community composition and survival strategies: a meta-analysis revealing trade-offs between microbial stability and functional complexity - Jianwei Li; Jeewani H. Peduruhewa; Robert W. Brown; David R. Chadwick; Robert I. Griffiths; Haoran Fu; Hongfeng Bian; LianXi Sheng; Qinqxu Ma; Davey L. Jones (Biology and Fertility of Soils, 2026)
As a promising strategy for improving soil health and mitigating climate change, biochar has received increasing attention in recent years. However, findings regarding its microbial effects are often context-dependent, and the complex impacts of biochar on soil microbial communities remain inadequately understood. Here, we integrated 843 samples of 16 S rRNA sequencing data from 24 independent studies, utilizing machine learning and co-occurrence network analysis to evaluate general patterns and mechanisms by which biochar alters bacteria community composition and survival strategies. Overall, biochar significantly increased soil organic C, total N, pH, and reduced bulk density, which in turn affected microbial communities. While biochar addition did not notably alter bacterial α-diversity (Shannon index or species richness), it significantly changed β-diversity, indicating that biochar addition altered microbial community composition. Biochar changed community composition and survival strategies by reducing the oligotroph/copiotroph ratio, favouring copiotrophs groups (e.g., Bacteroidota). K -strategists (e.g., Planctomycetota) were reduced by biochar, potentially due to increased nutrient availability and increased competition. Model selection analysis identified that soil physicochemical properties were key drivers of α-diversity, while climate variables were the main factors influencing β-diversity. Biochar properties represented key factors influencing changes in microbial survival strategy. Machine learning identified 138 biomarker genera, with biochar-treated soils showing an increase in Pseudomonadota. Co-occurrence network analysis indicated that biochar increased microbial stability, but reduced network complexity, suggesting a trade-off between resilience and functional redundancy following biochar addition. These findings provide new insights into how biochar influences the composition and ecological functions of soil bacterial communities and offer theoretical support for its scientific application in sustainable soil management.

Reliable identification of flood-borne deposits in speleothems using magnetic microscopy - Samuel L. Piascik; Roger R. Fu; Nicolás M. Stríkis; Ricardo I.F. Trindade; Julio Cauhy Rodrigues; Francisco W. Cruz; Gelson F. Souza-Junior; Andrea Borsato; Vitor Azevedo; Plinio Jaqueto; Isabel Tamara Pedron; Perri Thaler; et al. (Quaternary Science Reviews, 2025)

Prof Stephen P. Long, FRS (1950–2025) - Lorenzo Álvarez‐Filip; Edith Bai; Carl J. Bernacchi; Rhea Bruno; Klaus Butterbach‐Bahl; Maria Byrne; I‐Ching Chen; Shaolin Chen; William W. L. Cheung; M. Francesca Cotrufo; Tatenda Dalu; Xiaojuan Feng; et al. (Global Change Biology, 2025)

Metagenomics reveals diverse community of putative mercury methylators across different biogeochemical niches in Sansha Yongle blue hole - Heyu Lin; Xiao-Yu Zhu; Chun-Xu Xue; Peng Yao; Liang Fu; Zuosheng Yang; Xiao-Hua Zhang; John W. Moreau (Marine Life Science & Technology, 2025)
Methylmercury (MeHg) is a potent neurotoxin and bioaccumulates in food webs. Microbial transformation of inorganic mercury (Hg) produces most of the MeHg in the marine environment. The gene pair hgcAB encodes for Hg methylation, a process predominantly attributed to anaerobic bacteria. However, recent studies indicate the formation of methylmercury in low-oxygen zones within marine water columns, although the mechanisms remain poorly understood. “Blue holes” are marine sinkholes containing redox gradients stratified with depth and high microbial diversity across a range of biogeochemical cycles. Here, we present the first metagenomic analysis focused on the potential for Hg methylation in a blue hole ecosystem. Yongle Blue Hole (YBH), currently the world’s deepest known blue hole, was selected as a representative site to investigate the genetic potential for Hg methylation and to explore the functional capabilities of putative Hg-methylators within this unique environment. Metagenomic analysis showed that the anoxic sulfidic deep water was likely to be a hotspot for Hg methylation, driven by abundant and diverse Deltaproteobacteria. In the suboxic intermediate layer, Nitrospina and Myxococcota dominated the Hg-methylating community. Furthermore, Hg methylators were found to have different lifestyles (free-living or particle-associated) and to occupy distinct ecological niches within the YBH. In addition, the contribution of sinking particles to Hg methylation, especially in the deep anoxic water column, was highlighted. Our study unveils the biodiversity and survival strategies of Hg methylators across distinct environments. The findings suggest that blue holes could serve as model stratified ecosystems for studying Hg methylation processes across different habitats.

Metallogenic age and geological significance of the Jiazishan Mo deposit, Inner Mongolia, China - Z. L. Wang; J. Z. Yang; K. Q. Zhao; Y. G. Fu; J. W. Gao; Y. M. Deng; L. J. Lin; Z. Duan (Australian Journal of Earth Sciences, 2025)

A commentary on strategic community-led directions for water quality modelling in Australia and New Zealand - Danlu Guo; Anna Lintern; Alexander H. Elliott; Melanie E. Roberts; Susan M. Cuddy; Ulrike Bende-Michl; Baihua Fu; Klaus Joehnk; Robert Sargent; Danswell Starrs; Anthony J. Jakeman; Vaughn Grey; et al. (Journal of Hydrology, 2025)

Cotton3DGaussians: Multiview 3D Gaussian Splatting for boll mapping and plant architecture analysis - Lizhi Jiang; Jin Sun; Peng W. Chee; Changying Li; Longsheng Fu (Computers and Electronics in Agriculture, 2025)

Towards an understanding of dynamics of blue-ice moraines: A case study in the Grove Mountains, East Antarctica - Guocheng Dong; Feixin Huang; Weijian Zhou; Yunchong Fu; Yan Li; Feng Xian; Chaolu Yi; Marc W. Caffee; Xiaohan Liu (Geomorphology, 2025)

Plastic degradation in Lake Geneva: Influence of depth, seasonal shifts, and bacterial community dynamics - Laureen Mori-Bazzano; Nhung H.A. Nguyen; Alena Sevcu; Jakub Riha; Tingting Fu; Vera I. Slaveykova; Bastiaan W. Ibelings (Science of The Total Environment, 2025)

Sea level rise submergence simulations suggest substantial deterioration of Indian River Lagoon ecosystem services likely by 2050, Florida, USA - Randall W. Parkinson; Levente Juhasz; Shimon Wdowinski; Valerie Seidel; Jennifer Fu (Regional Environmental Change, 2025)

Mapping the landscape of bird strike research: insights from a quantitative analysis - H. X. Wang; W. Fu; N. A. Razak; Y. Y. Shi (International Journal of Environmental Science and Technology, 2025)

Living with bats: polyphasic approach reveals a new Fusarium species in Yunnan Province, China - Xiang‐Fu Liu; Saowaluck Tibpromma; Alice C. Hughes; Kevin D. Hyde; Abdallah M. Elgorban; Salim S. Al‐Rejaie; K. W. Thilini Chethana; Samantha C. Karunarathna (New Zealand Journal of Botany, 2025)
Bats are one of the most diverse mammal groups, with over 1400 species distributed across the planet, and they provide key ecological and economic services. In addition, bats provide an ideal habitat for fungal growth and harbour a high diversity of fungal species. Previous studies have described 423 fungal species associated with bats and bat carcasses. This paper describes a new fungal species, Fusarium rhinolophi, belonging to Nectriaceae, collected from bats in Mengla County, Xishuangbanna Dai Autonomous Prefecture, Yunnan Province, China. Phylogenetic analyses of the combined ITS, CAM , TEF‐1α , TUB , RPB1 , and RPB2 dataset confirmed that our fungus forms an independent lineage within the F. nisikadoi species complex. Thus, we describe our fungus as a new species of Fusarium based on morphology and molecular phylogeny. A description, phylogenetic tree showing species placement, and micrographs are provided.

Study of D s 1 ( 2460 ) + → D s + π + π - in B → D ‾ ( * ) D s + π + π - decays - R. Aaij; A.S.W. Abdelmotteleb; C.Abellan Beteta; F. Abudinén; T. Ackernley; A.A. Adefisoye; B. Adeva; M. Adinolfi; P. Adlarson; C. Agapopoulou; C.A. Aidala; Z. Ajaltouni; et al. (Science Bulletin, 2025)

Correction to: Deep plastid phylogeographic divergence of beaked hickory (Carya sinensis) calls for transboundary conservation in a biodiversity hotspot - Xiao-Yu Song; Moses C. Wambulwa; Richard Milne; Winnie W. Mambo; Zeng-Yuan Wu; Zhong-Hu Li; Ya-Huang Luo; Dinh Duy Vu; Jie Cai; Guang-Fu Zhu; Zhi-Peng Li; Lei Cai; et al. (Tree Genetics & Genomes, 2025)

Unraveling the edaphic factors driving organic material decay: Insights from long-term manure application studies - Yuting Fu; Sabine Ravnskov; Marcos Paradelo; Lis W. de Jonge; Emmanuel Arthur (Soil Biology and Biochemistry, 2025)

Ammonia inhibition in anaerobic digestion of organic waste: a review - J. Yang; J. Zhang; X. Du; T. Gao; Z. Cheng; W. Fu; S. Wang (International Journal of Environmental Science and Technology, 2025)
Anaerobic digestion (AD) has become the technology of choice for organic waste treatment as an environmentally beneficial and sustainable waste treatment technology. However, the nitrogen content of these organic waste streams is generally high. Ammonia is produced in the biodegradation of nitrogenous organic matter. Low concentrations of ammonia favour AD, but high concentrations can lead to digestive system failure. To address the issue of ammonia inhibition and ensure the stability of the digestive system, numerous physical, chemical, and biologicalmethods aimed at controlling ammonia levels and/or strengthening the biological processes have been proposedand developed. Literature evidence suggests that differences in AD reaction conditions and microbial sources result in different tolerances of the digestive system to ammonia and nitrogen. This paper summarises and compares the inhibitory effects of ammonia nitrogen under different conditions and the existing regulatory measures to alleviate ammonia nitrogen inhibition. In addition, since the core of the digestive system is microorganisms, this paper explains the mechanism of ammonia stress especially at the microbial level, and in this way, it explores the future direction of research using biofortification. This review provides a theoretical reference for solving the problem of ammonia nitrogen inhibition.

Effects of plant invasion and land use change on soil labile organic carbon in southern China’s coastal wetlands - Lihua Wang; Wenjing Liu; Xueya Zhou; Shenglei Fu; Ping Yang; Chuan Tong; Hong Yang; Dongyao Sun; Linhai Zhang; Wanyi Zhu; Kam W. Tang (Soil Ecology Letters, 2025)

Incorporating Genetic Diversity to Optimize the Plant Conservation Network in the Third Pole - Moses C. Wambulwa; Guang‐Fu Zhu; Ya‐Huang Luo; Zeng‐Yuan Wu; Jim Provan; Marc W. Cadotte; Alistair S. Jump; Francis N. Wachira; Lian‐Ming Gao; Ting‐Shuang Yi; Jie Cai; Hong Wang; et al. (Global Change Biology, 2025)
Climate change poses a significant threat to the survival of many species. Although protected areas can slow down biodiversity loss, they often lack systematic planning and do not integrate genetic diversity. Genetic diversity is a key prerequisite for species survival and the ability to tolerate new conditions. Using population genetic and distribution data from 96 plant species in the Third Pole (encompassing the Tibetan Plateau and adjacent mountains), we mapped patterns of genetic diversity, projected climate‐driven range dynamics and future genetic erosion, and designed an optimal conservation framework for the region. We identified several patches of high haplotype diversity ( H D ), with a relatively high number of haplotypes in southeastern Third Pole. Regression models revealed that climate and topography have interacted to shape patterns of genetic diversity, with latitude and precipitation being the best predictors for H D of cpDNA and nrDNA, respectively. Ecological niche modeling predicted an approximate 43 km northwestward and 86 m upward shift in suitable habitats under future climate scenarios, likely leading to a significant loss of up to 13.19% and 15.49% of cpDNA and nrDNA genetic diversity, respectively. Alarmingly, 71.20% of the newly identified conservation priority areas fall outside of the existing protected areas and planned National Park Clusters. Therefore, we recommend expanding the network by 2.02 × 10 5 km 2 (5.91%) in the Third Pole, increasing the total conserved area to 1.36 × 10 6 km 2 (39.93%) to effectively preserve the evolutionary potential of plants. This study represents an innovative attempt to incorporate genetic diversity into biodiversity conservation efforts.

Measurement of the decay Ξ 0 → Λ γ with entangled Ξ 0 Ξ ¯ 0 pairs - M. Ablikim; M.N. Achasov; P. Adlarson; O. Afedulidis; X.C. Ai; R. Aliberti; A. Amoroso; Q. An; Y. Bai; O. Bakina; I. Balossino; Y. Ban; et al. (Science Bulletin, 2025)

Amyloid fibrils for β-carotene delivery – Influence of self-assembled structures on binding and in vitro release behavior - Congying Chen; Haifeng Wang; Qing Wang; Mengting Wang; David W. Everett; Min Huang; Yun Zhai; Teng Li; Yuying Fu (Food Chemistry, 2025)

Deep plastid phylogeographic divergence of beaked hickory (Carya sinensis) calls for transboundary conservation in a biodiversity hotspot - Xiao-Yu Song; Moses C. Wambulwa; Richard Milne; Winnie W. Mambo; Zeng-Yuan Wu; Zhong-Hu Li; Ya-Huang Luo; Dinh Duy Vu; Jie Cai; Guang-Fu Zhu; Zhi-Peng Li; Lei Cai; et al. (Tree Genetics & Genomes, 2024)

Future Shorelines: A Living Shoreline Site Selection and Design Decision Support Tool that Incorporates Future Conditions Induced by Sea Level Rise - Randall W. Parkinson; Levente Juhasz; Jinwen Xu; Zhaohui Jennifer Fu (Estuaries and Coasts, 2024)
Most living shoreline site selection and design decision support tools are based upon existing environmental conditions. We developed a web-based, geospatial tool called Future Shorelines that integrates high-resolution landscape elevation data and a matrix of locally derived NOAA Interagency Sea Level Rise Scenarios to characterize future conditions of submergence and shoreline translation induced by sea level rise. Once the practitioner selects a location of interest, sea level rise scenario (e.g., high), and target year (e.g., 2050), the tool will generate plan view and cross-sectional informational graphics specific to their choices. This information can then be paired with other menu options, like parcel ownership, to facilitate the planning and construction of nature-based shoreline stabilization solutions that (1) are located where opportunities for horizontal migration are optimized, (2) remain accessible for monitoring and maintenance, and (3) perform as intended over the design life of the installation. The tool’s menu options and the user interface were informed by project partner input solicited during numerous workshops convened over the duration of the 2-year project. This coproduction created a product that was familiar to the end user and therefore increased the likelihood that it would be utilized by them during the planning and design of living shoreline projects. Although developed for use in the Indian River Lagoon, located along the east-central Florida coast, it can be seamlessly replicated for application in other coastal regions of the USA where the requisite data are available.

Hydroxypropyl methycellulose-galactomannan binary complexes achieving 55 wt% curcumin loading capacity: Mechanism and bioactivity - Haifeng Wang; Chenhui Wang; Jiang Mou; Yuting Wang; David W. Everett; Wenle He; Teng Li; Yuying Fu (Food Hydrocolloids, 2024)

Using a GFP-labeled Stagonospora nodorum strain as a DNA extraction efficiency standard in plant disease diagnosis - Heting Fu; Yalong Yang; Kher Zahr; Shiming Xue; Junye Jiang; Michael W. Harding; David Feindel; Jie Feng (Crop Protection, 2024)

Combination and summary of ATLAS dark matter searches interpreted in a 2HDM with a pseudo-scalar mediator using 139 fb−1 of s = 13 TeV pp collision data - G. Aad; B. Abbott; K. Abeling; N.J. Abicht; S.H. Abidi; A. Aboulhorma; H. Abramowicz; H. Abreu; Y. Abulaiti; A.C. Abusleme Hoffman; B.S. Acharya; C. Adam Bourdarios; et al. (Science Bulletin, 2024)

Prospects for Neotropical Forest Birds and Their Habitats Under Contrasting Emissions Scenarios - Jeffrey D. Brawn; David Luther; Mingxin Qu; Sarah M. Farinelli; W. Justin Cooper; Rong Fu (Global Change Biology, 2024)
Current and near future climate policy will fundamentally influence the integrity of ecological systems. The Neotropics is a region where biodiversity is notably high and precipitation regimes largely determine the ecology of most organisms. We modeled possible changes in the severity of seasonal aridity by 2100 throughout the Neotropics and used birds to illustrate the implications of contrasting climate scenarios for the region's biodiversity. Under SSP‐8.5, a pessimistic and hopefully unlikely scenario, longer dry seasons (> 5%), and increased moisture stress are projected for about 75% of extant lowland forests throughout the entire region with impacts on 66% of the region's lowland forest avifauna, which comprises over 3000 species and about 30% of all bird species globally. Longer dry seasons are predicted to be especially significant in the Caribbean, Upper South America, and Amazonia. In contrast, under SSP‐2.6—a scenario with significant climate mitigation—only about 10% of the entire region's forest area and 3% of its avifauna will be exposed to longer dry seasons. The extent of current forest cover that may plausibly function as precipitation‐based climate refugia (i.e.,

Phase separation and gelation of gelatin-glucose syrup mixtures and gummy confections: Effects of moisture content, sugars, citric acid, and citrates - Ruican Wang; Richard W. Hartel; Xinyu Zhai; Wenhui Fu; Yi Sun; Shuo Wang (Food Hydrocolloids, 2024)

MSC-Derived Extracellular Vesicles Alleviate NLRP3/GSDMD-Mediated Neuroinflammation in Mouse Model of Sporadic Alzheimer’s Disease - Lishan Lin; Longxin Huang; Sen Huang; Weineng Chen; Heng Huang; Li Chi; Fengjuan Su; Xiaoqing Liu; Kang Yuan; Qiuhong Jiang; Changu Li; Wanli W. Smith; et al. (Molecular Neurobiology, 2024)

Saprobic Dothideomycetes from Yunnan, China: introducing a new species, Queenslandipenidiella lingcangensis , and a new host record for Periconia byssoides - Guang-Cong Ren; Er-Fu Yang; Jutamart Monkai; Kandawatte W. T. Chethana; Heng Gui; Antonio Roberto Gomes de Farias (New Zealand Journal of Botany, 2024)

Plenodomus tracheiphilus, but not Dothiorella ulmi, causes wilt disease on elm trees in Alberta, Canada - Yalong Yang; Heting Fu; Kher Zahr; Shiming Xue; James Calpas; Krista Demilliano; Michael W. Harding; David Feindel; Jie Feng (European Journal of Plant Pathology, 2024)

Investigating speleothem magnetism as a proxy for dust mobilization and rainfall - Kimberly Hess; Roger R. Fu; Samuel Piascik; Nicolas M. Stríkis; Ricardo I.F. Trindade; Tyler Kukla; Alec R. Brenner; Plinio Jaqueto; Michail I. Petaev; Francisco W. Cruz; Placido Fabricio Silva Melo Buarque; Carlos Pérez-Mejías; et al. (Quaternary Science Reviews, 2024)

Parametric design, life cycle assessment, and optimization of a discrete product with application to an electric traction motor - Jesús R. Pérez-Cardona; Thomas Maani; Fu Zhao; John W. Sutherland (Resources, Conservation and Recycling, 2024)

Process development and techno-economic analysis for mechanochemical recycling of poly(ethylene terephthalate) - Elisavet Anglou; Arvind Ganesan; Yuchen Chang; Kinga M. Gołąbek; Qiang Fu; William Bradley; Christopher W. Jones; Carsten Sievers; Sankar Nair; Fani Boukouvala (Chemical Engineering Journal, 2024)

Correction to: Clinical Significance and Influencing Factors of Microvascular Tissue Reperfusion After Macrovascular Recanalization - Xuesong Bai; Fan Yu; Qiuyue Tian; Wei Li; Arman Sha; Wenbo Cao; Yao Feng; Bin Yang; Yanfei Chen; Peng Gao; Yabing Wang; Jian Chen; et al. (Translational Stroke Research, 2023)

16s-RNA sequencing analysis of the influence of UV radiation on the metabolic pathways of pollutants in the A2O process - Y. W. Li; J. H. You; Y. C. Zong; J. Wang; C. H. Fu (International Journal of Environmental Science and Technology, 2023)

Partial C-terminal truncation of Bx and Dy high molecular weight glutenin subunits after conserved aspartate - Ray Bacala; Dave W. Hatcher; Héléne Perreault; Bin Xiao Fu (Journal of Cereal Science, 2023)

Using in-situ strain measurements to evaluate the accuracy of stress estimation procedures from fracture injection/shut-in tests - Yves Guglielmi; Mark McClure; Jeffrey Burghardt; Joseph P. Morris; Thomas Doe; Pengcheng Fu; Hunter Knox; Vince Vermeul; Tim Kneafsey; J. Ajo-Franklin; T. Baumgartner; K. Beckers; et al. (International Journal of Rock Mechanics and Mining Sciences, 2023)

Clinical Significance and Influencing Factors of Microvascular Tissue Reperfusion After Macrovascular Recanalization - Xuesong Bai; Fan Yu; Qiuyue Tian; Wei Li; Araman Sha; Wenbo Cao; Yao Feng; Bin Yang; Yanfei Chen; Peng Gao; Yabing Wang; Jian Chen; et al. (Translational Stroke Research, 2023)

Cerebrospinal fluid levels of 5-HIAA and dopamine in people with HIV and depression - Rong Fu; Hyder Jinnah; J. Lucas Mckay; Andrew H. Miller; Jennifer C. Felger; Eugene W. Farber; Sanjay Sharma; Neil Whicker; Raeanne C. Moore; Donald Franklin; Scott L. Letendre; Albert M. Anderson (Journal of NeuroVirology, 2023)

The mobility and fate of Cr during aging of ferrihydrite and ferrihydrite organominerals - Yao Zhao; Alba Otero-Fariña; Ke-Qing Xiao; Oliver W. Moore; Steven A. Banwart; Fu-Jun Ma; Qing-Bao Gu; Caroline L. Peacock (Geochimica et Cosmochimica Acta, 2023)

The diversity of mycorrhiza‐associated fungi and trees shapes subtropical mountain forest ecosystem functioning - Ya‐Huang Luo; Liang‐Liang Ma; Sebastian Seibold; Marc W. Cadotte; Kevin S. Burgess; Shao‐Lin Tan; Lin‐Jiang Ye; Wei Zheng; Jia‐Yun Zou; Zhi‐Fa Chen; De‐Tuan Liu; Guang‐Fu Zhu; et al. (Journal of Biogeography, 2023)
Aim Mycorrhiza play key roles for ecosystem structure and functioning in forests. However, how different mycorrhizal types influence mountain forest biodiversity–ecosystem functioning (BEF) relationships are largely unknown. We evaluate how the diversity of distinct mycorrhiza‐associated fungi and trees shapes forest carbon storage along elevational gradients. Location Gaoligong Mountains within Hengduan Mountains, Southwest China. Taxon Seed plants and mycorrhizal fungi. Methods We used the data from 31 subtropical forest plots along elevational gradients on two aspects (east and west) of the mountain. We quantified species richness of trees and symbiotic fungi and assigned both to their mycorrhizal type (arbuscular mycorrhiza [AM], ectomycorrhiza [EcM] and ericoid mycorrhiza [ErM]). We then examined the diversity effects of mycorrhiza‐associated fungi and trees on above‐ground carbon stored in trees and organic carbon stored in soils. Results Species richness was highest for AM trees (79.5%), followed by ErM trees (13.4%) and then EcM trees (7.1%). Species richness of AM‐associated trees and fungi decreased with increasing elevation, while ErM‐associated trees and fungi showed an opposite trend. EcM‐associated diversity followed a hump‐shaped relationship with elevation. Positive relationships between diversity and above‐ground carbon were detected in all three mycorrhizal associations, but despite low species number, canopy‐dominating EcM trees comprised 64.4% of the amount of above‐ground carbon. Furthermore, community‐weighted means of height exhibited positive correlations with forest above‐ground carbon, indicating that positive selection effects occur. Soil organic carbon was positively related to EcM‐associated fungi diversity, above‐ground carbon mass and soil nitrogen availability, with the latter having strongest direct effects. Main Conclusions The distributions of forest biodiversity and carbon storage can be modulated by distinct mycorrhizal fungi and trees. Moreover, future global changes (e.g. climate warming, intensifying nitrogen deposition) could alter the mycorrhizal‐mediated BEF relationships in mountain forests.

Growth of winter wheat adapting to climate warming may face more low‐temperature damage - Yanling Song; Guangsheng Zhou; Hans W. Linderholm; Junfang Wang; Yong Li; Guofu Wang; Yan Fu; Jinxia Xu; Ying Shi; Ying Xu; Hui Gao; Deliang Chen (International Journal of Climatology, 2023)
China's surface air temperature is increasing due to global warming, so it is interesting that how low temperatures would be changed during the growth period of winter wheat in future. We focused on the low temperatures of winter wheat from 2021 to 2050, using temperatures under the high emission scenario Representative Concentration Pathway 8.5 (RCP8.5) projected by the RegCM4.4 regional climate model. The results showed that the annual mean temperature was projected to increase by 0.42°C⋅decade −1 in the northern and by 0.35°C⋅decade −1 in the southern winter wheat region. Furthermore, the temperature was expected to increase rapidly in spring, which could advance the dates of flowering and the start of the grain‐filling period. Using the genetic parameters determined by the calibration and validation of WOFOST and bias‐corrected projected meteorological data, simulations of winter wheat growth were performed over the winter wheat region for 2021–2050. The simulated number of days to the flowering period of winter wheat for 2041–2050 was on average 6.5 days less than in 2021–2030, due to the spring warming. Because of the earlier start of the growing season, winter wheat could face negative effects by being subjected to low temperatures. Indeed, the number of low‐temperature days was projected to increase by 110% from 2041 to 2050 compared to 2021–2030, and the number of killing degree days (KDDs) is projected to increase by 120% at the same time. If the number of days to flowering did not change, the number of low‐temperature days and KDDs only changed slightly, showing that the negative influence of low temperature was mainly caused by the advancement of the flowering date. The effect of low temperature on growth was underestimated when the response of winter wheat growth to global warming was not considered.

Periostin regulation and cartilage degradation early after anterior cruciate ligament reconstruction - Cale A. Jacobs; Laura E. Keller; Sheng Zhang; Qin Fu; Emily R. Hunt; Austin V. Stone; Caitlin E. W. Conley; Christian Lattermann; Lisa A. Fortier (Inflammation Research, 2023)

Ecophysiological and genomic analyses of a representative isolate of highly abundant Bacillus cereus strains in contaminated subsurface sediments - Jennifer L. Goff; Elizabeth G. Szink; Michael P. Thorgersen; Andrew D. Putt; Yupeng Fan; Lauren M. Lui; Torben N. Nielsen; Kristopher A. Hunt; Jonathan P. Michael; Yajiao Wang; Daliang Ning; Ying Fu; et al. (Environmental Microbiology, 2022)
Bacillus cereus strain CPT56D‐587‐MTF (CPTF) was isolated from the highly contaminated Oak Ridge Reservation (ORR) subsurface. This site is contaminated with high levels of nitric acid and multiple heavy metals. Amplicon sequencing of the 16S rRNA genes (V4 region) in sediment from this area revealed an amplicon sequence variant (ASV) with 100% identity to the CPTF 16S rRNA sequence. Notably, this CPTF‐matching ASV had the highest relative abundance in this community survey, with a median relative abundance of 3.77% and comprised 20%–40% of reads in some samples. Pangenomic analysis revealed that strain CPTF has expanded genomic content compared to other B. cereus species—largely due to plasmid acquisition and expansion of transposable elements. This suggests that these features are important for rapid adaptation to native environmental stressors. We connected genotype to phenotype in the context of the unique geochemistry of the site. These analyses revealed that certain genes (e.g. nitrate reductase, heavy metal efflux pumps) that allow this strain to successfully occupy the geochemically heterogenous microniches of its native site are characteristic of the B. cereus species while others such as acid tolerance are mobile genetic element associated and are generally unique to strain CPTF.

Controlling Hydraulic Fracture Growth Through Precise Vertical Placement of Lateral Wells: Insights from HFTS Experiment and Numerical Validation - W. Fu; J. P. Morris; C. S. Sherman; P. Fu; J. Huang (Rock Mechanics and Rock Engineering, 2022)

Understorey light environment impacts on seedling establishment and growth in a typhoon-disturbed tropical forest - Kuo-Jung Chao; Yung-Chiau Lin; Guo-Zhang Michael Song; Chien-Hui Liao; Yau-Lun Kuo; Chang-Fu Hsieh; Eugene W. Schupp (Plant Ecology, 2022)

TREM-2 mediates dendritic cell–induced NO to suppress Th17 activation and ameliorate chronic kidney diseases - Ching-Cheng Lin; Ti-Yung Chang; Yong-Chen Lu; Yun-Syuan Wu; Wei Huang; Wei-Chi Lo; Guan-Fu Liu; Wei-Chan Hsu; Pamela S. Ohashi; Tak W. Mak; Jong-Ling Fuh; Hui-Chen Chen; et al. (Journal of Molecular Medicine, 2022)

Oral Enrichment of Streptococcus and its Role in Systemic Inflammation Related to Monocyte Activation in Humans with Cocaine Use Disorder - Xiaoyu Fu; Da Cheng; Zhenwu Luo; Amanda Wagner; Sylvia Fitting; Xiaomei Cong; Wanli Xu; Kendra Maas; Zhuang Wan; Jian Zhu; Zejun Zhou; William W. Stoops; et al. (Journal of Neuroimmune Pharmacology, 2022)

Field engineering application of agricultural farmland surface runoff pollution treatment by combined bioreactor and constructed wetlands - H. Luo; X. Li; Y. Chen; X. Liu; K. Zhang; X. Fu; B. Jiang; R. Xue; J. Yang; M. Li; X. Li; W. Chen; et al. (International Journal of Environmental Science and Technology, 2022)

Surrogate Models in Rock and Soil Mechanics: Integrating Numerical Modeling and Machine Learning - J. K. Furtney; C. Thielsen; W. Fu; R. Le Goc (Rock Mechanics and Rock Engineering, 2022)

Demographic composition, not demographic diversity, predicts biomass and turnover across temperate and tropical forests - Jessica F. Needham; Daniel J. Johnson; Kristina J. Anderson‐Teixeira; Norman Bourg; Sarayudh Bunyavejchewin; Nathalie Butt; Min Cao; Dairon Cárdenas; Chia‐Hao Chang‐Yang; Yu‐Yun Chen; George Chuyong; Handanakere S. Dattaraja; et al. (Global Change Biology, 2022)
The growth and survival of individual trees determine the physical structure of a forest with important consequences for forest function. However, given the diversity of tree species and forest biomes, quantifying the multitude of demographic strategies within and across forests and the way that they translate into forest structure and function remains a significant challenge. Here, we quantify the demographic rates of 1961 tree species from temperate and tropical forests and evaluate how demographic diversity (DD) and demographic composition (DC) differ across forests, and how these differences in demography relate to species richness, aboveground biomass (AGB), and carbon residence time. We find wide variation in DD and DC across forest plots, patterns that are not explained by species richness or climate variables alone. There is no evidence that DD has an effect on either AGB or carbon residence time. Rather, the DC of forests, specifically the relative abundance of large statured species, predicted both biomass and carbon residence time. Our results demonstrate the distinct DCs of globally distributed forests, reflecting biogeography, recent history, and current plot conditions. Linking the DC of forests to resilience or vulnerability to climate change, will improve the precision and accuracy of predictions of future forest composition, structure, and function.

Plasmodiophora brassicae infection threshold—how many resting spores are required for generating clubroot galls on canola (Brassica napus) - Kher Zahr; Yalong Yang; Alian Sarkes; Snezana Dijanovic; Heting Fu; Michael W. Harding; David Feindel; Jie Feng (Journal of Plant Diseases and Protection, 2022)

Cycle Length Evaluation in Persistent Atrial Fibrillation Using Kernel Density Estimation to Identify Transient and Stable Rapid Atrial Activity - Szabolcs Z. Nagy; Patrick Kasi; Valtino X. Afonso; Nathaniel Bird; Brian Pederson; Ian E. Mann; Steven Kim; Nicholas W. F. Linton; David C. Lefroy; Zachary I. Whinnett; Fu Siong Ng; Michael Koa-Wing; et al. (Cardiovascular Engineering and Technology, 2022)
Purpose Left atrial (LA) rapid AF activity has been shown to co-localise with areas of successful atrial fibrillation termination by catheter ablation. We describe a technique that identifies rapid and regular activity. Methods Eight-second AF electrograms were recorded from LA regions during ablation for psAF. Local activation was annotated manually on bipolar signals and where these were of poor quality, we inspected unipolar signals. Dominant cycle length (DCL) was calculated from annotation pairs representing a single activation interval, using a probability density function (PDF) with kernel density estimation. Cumulative annotation duration compared to total segment length defined electrogram quality. DCL results were compared to dominant frequency (DF) and averaging. Results In total 507 8 s AF segments were analysed from 7 patients. Spearman’s correlation coefficient was 0.758 between independent annotators ( P < 0.001), 0.837–0.94 between 8 s and ≥ 4 s segments ( P < 0.001), 0.541 between DCL and DF ( P < 0.001), and 0.79 between DCL and averaging ( P < 0.001). Poorer segment organization gave greater errors between DCL and DF. Conclusion DCL identifies rapid atrial activity that may represent psAF drivers. This study uses DCL as a tool to evaluate the dynamic, patient specific properties of psAF by identifying rapid and regular activity. If automated, this technique could rapidly identify areas for ablation in psAF.

Documenting pollinators, floral hosts, and plant–pollinator interactions in U.S. P acific N orthwest agroecosystems - Elias H. Bloom; Elisabeth C. Oeller; Rachel L. Olsson; Matthew R. Brousil; Robert N. Schaeffer; Saumik Basu; Zhen Fu; David W. Crowder (Ecology, 2022)
The abundance and diversity of pollinator populations are in global decline. Managed pollinator species, like honey bees, and wild species are key ecosystem service providers in both natural and managed agroecosystems. However, relatively few studies have exhaustively characterized pollinator populations in diverse agroecosystems over multiple years, while also thoroughly documenting plant–pollinator interactions. Yet, such studies are needed to fulfill the national pollinator protection plans that have been released by the United States and other nations. Our research is among the first studies to respond to these directives by systematically documenting bee and plant biodiversity, bee–plant interactions, and bee‐mediated pollen movement in farming systems of the Pacific Northwest, USA. Our data provides insight into the processes mediating pollinator and plant community assembly, persistence, and resilience across landscapes with variable crop and landscape diversity and agroecosystem management practices. These data will also contribute to the development of a United States pollinator database, supporting the United States' plan to promote pollinators. With few publicly available data sets that systematically take account of agroecosystem practices, plant populations, and pollinators, our research will provide future users the means to conduct synesthetic studies of pollinators and ecosystem function in a period of rapid and global pollinator declines. There are no copyright or proprietary restrictions for research or teaching purposes. Usage of the data set must be cited.

Correction to: 2021 Taxonomic update of phylum Negarnaviricota (Riboviria: Orthornavirae), including the large orders Bunyavirales and Mononegavirales - Jens H. Kuhn; Scott Adkins; Bernard R. Agwanda; Rim Al Kubrusli; Sergey V. Alkhovsky; Gaya K. Amarasinghe; Tatjana Avšič-Županc; María A. Ayllón; Justin Bahl; Anne Balkema-Buschmann; Matthew J. Ballinger; Christopher F. Basler; et al. (Archives of Virology, 2021)

2021 Taxonomic update of phylum Negarnaviricota (Riboviria: Orthornavirae), including the large orders Bunyavirales and Mononegavirales - Jens H. Kuhn; Scott Adkins; Bernard R. Agwanda; Rim Al Kubrusli; Sergey V. Alkhovsky; Gaya K. Amarasinghe; Tatjana Avšič-Županc; María A. Ayllón; Justin Bahl; Anne Balkema-Buschmann; Matthew J. Ballinger; Christopher F. Basler; et al. (Archives of Virology, 2021)

Correction to: Bacterial etiology of community-acquired pneumonia in immunocompetent hospitalized patients and appropriateness of empirical treatment recommendations: an international point-prevalence study - Manuela Carugati; S. Aliberti; G. Sotgiu; F. Blasi; A. Gori; R. Menendez; M. Encheva; M. Gallego; P. Leuschner; S. Ruiz-Buitrago; S. Battaglia; R. Fantini; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2021)

Hyperoxia-induced S1P1 signaling reduced angiogenesis by suppression of TIE-2 leading to experimental bronchopulmonary dysplasia - Tara Sudhadevi; Anjum Jafri; Alison W. Ha; Prathima Basa; Jaya M. Thomas; Panfeng Fu; Kishore Wary; Dolly Mehta; Viswanathan Natarajan; Anantha Harijith (Cell Biochemistry and Biophysics, 2021)

Nuclear Sphingosine-1-phosphate Lyase Generated ∆2-hexadecenal is A Regulator of HDAC Activity and Chromatin Remodeling in Lung Epithelial Cells - David L. Ebenezer; Ramaswamy Ramchandran; Panfeng Fu; Lizar A. Mangio; Vidyani Suryadevara; Alison W. Ha; Evgeny Berdyshev; Paul P. Van Veldhoven; Stephen J. Kron; Fabian Schumacher; Burkhard Kleuser; Viswanathan Natarajan (Cell Biochemistry and Biophysics, 2021)

Characteristics and formation mechanisms of Mesozoic compressional structures in the Huanghua Depression, Bohai Bay Basin, China - W. Li; F. Zhang; Y. Zhang; L. Fu; H. Li (Australian Journal of Earth Sciences, 2021)

Downregulation of Adhesion Molecule CHL1 in B Cells but Not T Cells of Patients with Major Depression and in the Brain of Mice with Chronic Stress - C. R. Yang; L. Ning; F. H. Zhou; Q. Sun; H. P. Meng; Z. Han; Y. Liu; W. Huang; S. Liu; X. H. Li; B. Zheng; Dong Ming; et al. (Neurotoxicity Research, 2020)

Patterns of mitochondrial DNA fragmentation in bread wheat (Triticum aestivum L.) seeds under ex situ genebank storage and artificial aging - Yong-Bi Fu; Zaheer Ahmed; Hui Yang; Carolee Horbach; Gregory W. Peterson (Genetic Resources and Crop Evolution, 2020)

Low Static Shear Modulus Along Foliation and Its Influence on the Elastic and Strength Anisotropy of Poorman Schist Rocks, Homestake Mine, South Dakota - Katherine J. Condon; Hiroki Sone; Herbert F. Wang; J. Ajo-Franklin; T. Baumgartner; K. Beckers; D. Blankenship; A. Bonneville; L. Boyd; S. Brown; J. A. Burghardt; C. Chai; et al. (Rock Mechanics and Rock Engineering, 2020)

New gravimetric-only and hybrid geoid models of Taiwan for height modernisation, cross-island datum connection and airborne LiDAR mapping - Cheinway Hwang; Hung-Jui Hsu; W. E. Featherstone; Ching-Chung Cheng; Ming Yang; Wenhsuan Huang; Chong-You Wang; Jiu-Fu Huang; Kwo-Hwa Chen; Chi-Hsun Huang; Hechin Chen; Wen-Yi Su (Journal of Geodesy, 2020)

Diversity in the population of Fusarium graminearum isolated from wheat and corn in Alberta, Canada - Hafiz Ahmed; Qixing Zhou; Kher Zahr; Yalong Yang; Heting Fu; Alian Sarkes; Yingli Wang; Krista Zuzak; David Feindel; Greg C. Daniels; Michael W. Harding; Jie Feng (Journal of Plant Diseases and Protection, 2020)

Bacterial etiology of community-acquired pneumonia in immunocompetent hospitalized patients and appropriateness of empirical treatment recommendations: an international point-prevalence study - Manuela Carugati; S. Aliberti; G. Sotgiu; F. Blasi; A. Gori; R. Menendez; M. Encheva; M. Gallego; P. Leuschner; S. Ruiz-Buitrago; S. Battaglia; R. Fantini; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2020)

Geographically isolated Colorado potato beetle mediating distinct defense responses in potato is associated with the alteration of gut microbiota - Jie Wang; Zhou Gao; Mingyu Yang; Rongrong Xue; Hui Yan; Kaiyun Fu; Zhaojuan Zhang; Wenchao Guo; Gary W. Felton; Rensen Zeng (Journal of Pest Science, 2020)

SEASTAR: A Mission to Study Ocean Submesoscale Dynamics and Small-Scale Atmosphere-Ocean Processes in Coastal, Shelf and Polar Seas - Christine Gommenginger; Bertrand Chapron; Andy Hogg; Christian Buckingham; Baylor Fox-Kemper; Leif Eriksson; Francois Soulat; Clément Ubelmann; Francisco Ocampo-Torres; Bruno Buongiorno Nardelli; David Griffin; Paco Lopez-Dekker; et al. (Frontiers in Marine Science, 2019)

Population Genetics of Calotropis gigantea, a Medicinal and Fiber Resource Plant, as Inferred from Microsatellite Marker Variation in two Native Countries - Md. Rabiul Islam; Zhi-Zhong Li; Andrew W. Gichira; Mohammad Nur Alam; Peng-Cheng Fu; Guang-Wan Hu; Qing-Feng Wang; Ling-Yun Chen (Biochemical Genetics, 2019)

Towards Comprehensive Observing and Modeling Systems for Monitoring and Predicting Regional to Coastal Sea Level - Rui M. Ponte; Mark Carson; Mauro Cirano; Catia M. Domingues; Svetlana Jevrejeva; Marta Marcos; Gary Mitchum; R. S. W. van de Wal; Philip L. Woodworth; Michaël Ablain; Fabrice Ardhuin; Valérie Ballu; et al. (Frontiers in Marine Science, 2019)

Response Mechanism of Oviposition and Relevant Protein Expression of Bactrocera cucurbitae (Coquillet) to Short-Term High-Temperature Conditions - B Zeng; W Zhu; Y Fu; S Zhou (Neotropical Entomology, 2019)

Identification of Gangesia oligonchis Roitman & Freze, 1964 (Cestoda: Onchoproteocephalidea) from Tachysurus fulvidraco Richardson in central China: implications for the validity of Gangesia pseudobagrae Chen, 1962 - Pei P. Fu; Wen X. Li; Hong Zou; Dong Zhang; Shan G. Wu; Ming Li; Gui T. Wang; Bing W. Xi (Systematic Parasitology, 2019)

Genotyping-by-sequencing empowered genetic diversity analysis of Jordanian oat wild relative Avena sterilis - Nawal Al-Hajaj; Gregory W. Peterson; Carolee Horbach; Khaled Al-Shamaa; Nicholas A. Tinker; Yong-Bi Fu (Genetic Resources and Crop Evolution, 2018)

Real-World Variability in the Prediction of Intracranial Aneurysm Wall Shear Stress: The 2015 International Aneurysm CFD Challenge - Kristian Valen-Sendstad; Aslak W. Bergersen; Yuji Shimogonya; Leonid Goubergrits; Jan Bruening; Jordi Pallares; Salvatore Cito; Senol Piskin; Kerem Pekkan; Arjan J. Geers; Ignacio Larrabide; Saikiran Rapaka; et al. (Cardiovascular Engineering and Technology, 2018)

Isometric strength of the hip abductors and external rotators in athletes with and without patellar tendinopathy - Z. J. Zhang; W. C. Lee; G. Y. F. Ng; S. N. Fu (European Journal of Applied Physiology, 2018)

Front Cover - James A. Lutz; Tucker J. Furniss; Daniel J. Johnson; Stuart J. Davies; David Allen; Alfonso Alonso; Kristina J. Anderson‐Teixeira; Ana Andrade; Jennifer Baltzer; Kendall M. L. Becker; Erika M. Blomdahl; Norman A. Bourg; et al. (Global Ecology and Biogeography, 2018)

Global importance of large‐diameter trees - James A. Lutz; Tucker J. Furniss; Daniel J. Johnson; Stuart J. Davies; David Allen; Alfonso Alonso; Kristina J. Anderson‐Teixeira; Ana Andrade; Jennifer Baltzer; Kendall M. L. Becker; Erika M. Blomdahl; Norman A. Bourg; et al. (Global Ecology and Biogeography, 2018)
Aim To examine the contribution of large‐diameter trees to biomass, stand structure, and species richness across forest biomes. Location Global. Time period Early 21st century. Major taxa studied Woody plants. Methods We examined the contribution of large trees to forest density, richness and biomass using a global network of 48 large (from 2 to 60 ha) forest plots representing 5,601,473 stems across 9,298 species and 210 plant families. This contribution was assessed using three metrics: the largest 1% of trees ≥ 1 cm diameter at breast height (DBH), all trees ≥ 60 cm DBH, and those rank‐ordered largest trees that cumulatively comprise 50% of forest biomass. Results Averaged across these 48 forest plots, the largest 1% of trees ≥ 1 cm DBH comprised 50% of aboveground live biomass, with hectare‐scale standard deviation of 26%. Trees ≥ 60 cm DBH comprised 41% of aboveground live tree biomass. The size of the largest trees correlated with total forest biomass ( r 2 = .62, p r 2 = .45, p r 2 = .33, p r 2 = .17, p = .002). The concentration of biomass in the largest 1% of trees declined with increasing absolute latitude ( r 2 = .46, p r 2 = .31, p r 2 = .26, p Main conclusions Because large‐diameter trees constitute roughly half of the mature forest biomass worldwide, their dynamics and sensitivities to environmental change represent potentially large controls on global forest carbon cycling. We recommend managing forests for conservation of existing large‐diameter trees or those that can soon reach large diameters as a simple way to conserve and potentially enhance ecosystem services.

Analysis of the Spatial Variation and Identification of Factors Affecting the Water Resources Carrying Capacity Based on the Cloud Model - K. Cheng; Q. Fu; J. Meng; T. X. Li; W. Pei (Water Resources Management, 2018)

DNA Barcoding for Identification of Sugarcane Borers in China - J- D Wang; W- Z Wang; Z- L Lin; A Ali; H- Y Fu; M- T Huang; S- J Gao; R Wang (Neotropical Entomology, 2018)

Spike densities of the amygdala and neocortex reflect progression of kindled motor seizures - Yu-Lin Wang; Sheng-Fu Liang; Alvin W. Y. Su; Fu-Zen Shaw (Medical & Biological Engineering & Computing, 2018)

Phenological responses of Icelandic subarctic grasslands to short‐term and long‐term natural soil warming - Niki I. W. Leblans; Bjarni D. Sigurdsson; Sara Vicca; Yongshuo Fu; Josep Penuelas; Ivan A. Janssens (Global Change Biology, 2017)
The phenology of vegetation, particularly the length of the growing season ( LOS ; i.e., the period from greenup to senescence), is highly sensitive to climate change, which could imply potent feedbacks to the climate system, for example, by altering the ecosystem carbon (C) balance. In recent decades, the largest extensions of LOS have been reported at high northern latitudes, but further warming‐induced LOS extensions may be constrained by too short photoperiod or unfulfilled chilling requirements. Here, we studied subarctic grasslands, which cover a vast area and contain large C stocks, but for which LOS changes under further warming are highly uncertain. We measured LOS extensions of Icelandic subarctic grasslands along natural geothermal soil warming gradients of different age (short term, where the measurements started after 5 years of warming and long term, i.e., warmed since ≥50 years) using ground‐level measurements of normalized difference vegetation index. We found that LOS linearly extended with on average 2.1 days per °C soil warming up to the highest soil warming levels (ca. +10°C) and that LOS had the potential to extend at least 1 month. This indicates that the warming impact on LOS in these subarctic grasslands will likely not saturate in the near future. A similar response to short‐ and long‐term warming indicated a strong physiological control of the phenological response of the subarctic grasslands to warming and suggested that genetic adaptations and community changes were likely of minor importance. We conclude that the warming‐driven extension of the LOS s of these subarctic grasslands did not saturate up to +10°C warming, and hence that growing seasons of high‐latitude grasslands are likely to continue lengthening with future warming (unless genetic adaptations or species shifts do occur). This persistence of the warming‐induced extension of LOS has important implications for the C‐sink potential of subarctic grasslands under climate change.

Value recovery from end-of-use products facilitated by automated dismantling planning - Liang Cong; Fu Zhao; John W. Sutherland (Clean Technologies and Environmental Policy, 2017)

The epigenetic modifications and the anterior to posterior characterization of meiotic entry during mouse oogenesis - Xia-Fei Fu; Fan Yang; Shun-Feng Cheng; Yan-Ni Feng; Lan Li; Paul W. Dyce; Wei Shen; Xiao-Feng Sun (Histochemistry and Cell Biology, 2017)

Alterations in mechanical properties of the patellar tendon is associated with pain in athletes with patellar tendinopathy - W. C. Lee; Z. J. Zhang; L. Masci; G. Y. F. Ng; Siu Ngor Fu (European Journal of Applied Physiology, 2017)

Role of the lipid-regulated NF-κB/IL-6/STAT3 axis in alpha-naphthyl isothiocyanate-induced liver injury - Zhong-Ze Fang; Naoki Tanaka; Dan Lu; Chang-Tao Jiang; Wei-Hua Zhang; Chunze Zhang; Zuo Du; Zhi-Wei Fu; Peng Gao; Yun-Feng Cao; Hong-Zhi Sun; Zhi-Tu Zhu; et al. (Archives of Toxicology, 2017)

Differences between serum polar lipid profiles of male and female rheumatoid arthritis patients in response to glucocorticoid treatment - Junzeng Fu; Bart V. J. Cuppen; Paco M. J. Welsing; Herman van Wietmarschen; Amy C. Harms; Ruud Berger; Slavik Koval; Ruth D. E. Fritsch-Stork; Johannes W. J. Bijlsma; Thomas Hankemeier; Jan van der Greef; Floris P. J. G. Lafeber (Inflammopharmacology, 2016)

Time Course Field Analysis of COMT-Downregulated Switchgrass: Lignification, Recalcitrance, and Rust Susceptibility - Holly L. Baxter; Mitra Mazarei; Chunxiang Fu; Qunkang Cheng; Geoffrey B. Turner; Robert W. Sykes; Mark T. Windham; Mark F. Davis; Richard A. Dixon; Zeng-Yu Wang; C. Neal Stewart (BioEnergy Research, 2016)

Fast neutron-induced structural rearrangements at a soybean NAP1 locus result in gnarled trichomes - Benjamin W. Campbell; Anna N. Hofstad; Suma Sreekanta; Fengli Fu; Thomas J. Y. Kono; Jamie A. O’Rourke; Carroll P. Vance; Gary J. Muehlbauer; Robert M. Stupar (Theoretical and Applied Genetics, 2016)

Myeloid leukemia factor 1 interfered with Bcl-XL to promote apoptosis and its function was regulated by 14-3-3 - Yi Sun; Amina Fu; Wu Xu; Jyh-Rong Chao; Simon Moshiach; Stephan W Morris (Journal of Physiology and Biochemistry, 2015)

Catalytic behavior and synergistic effect of nonthermal plasma and CuO/AC catalyst for benzene destruction - C. He; L. Cao; X. Liu; W. Fu; J. Zhao (International Journal of Environmental Science and Technology, 2015)

Scale dependence of the beta diversity-scale relationship - Y. Zhang; K. Ma; M. Anand; W. Ye; B. Fu (Community Ecology, 2015)

Efficiency and Accuracy Verification of the Explicit Numerical Manifold Method for Dynamic Problems - X. L. Qu; Y. Wang; G. Y. Fu; G. W. Ma (Rock Mechanics and Rock Engineering, 2015)

Pharmacokinetics, Antitumor and Cardioprotective Effects of Liposome-Encapsulated Phenylaminoethyl Selenide in Human Prostate Cancer Rodent Models - Jeong Yeon Kang; Mathew Eggert; Shravanthi Mouli; Ibrahim Aljuffali; Xiaoyu Fu; Ben Nie; Amy Sheil; Kendall Waddey; Charlie D. Oldham; Sheldon W. May; Rajesh Amin; Robert D. Arnold (Pharmaceutical Research, 2015)

Identification of the trehalose-6-phosphate synthase gene family in winter wheat and expression analysis under conditions of freezing stress - D. W. XIE; X. N. WANG; L. S. FU; J. SUN; W. ZHENG; Z. F. LI (Journal of Genetics, 2015)

Accuracy and Reproducibility of Patient-Specific Hemodynamic Models of Stented Intracranial Aneurysms: Report on the Virtual Intracranial Stenting Challenge 2011 - S. Cito; A. J. Geers; M. P. Arroyo; V. R. Palero; J. Pallarés; A. Vernet; J. Blasco; L. San Román; W. Fu; A. Qiao; G. Janiga; Y. Miura; et al. (Annals of Biomedical Engineering, 2015)

The Development of Drug-Free Therapy for Prevention of Dental Caries - Fu Chen; Zhenshan Jia; Kelly C. Rice; Richard A. Reinhardt; Kenneth W. Bayles; Dong Wang (Pharmaceutical Research, 2014)

Field Evaluation of Different Wavelengths Light-Emitting Diodes as Attractants for Adult Aleurodicus dispersus Russell (Hemiptera: Aleyrodidae) - L X Zheng; Y Zheng; W J Wu; Y G Fu (Neotropical Entomology, 2014)

The population genomic landscape of human genetic structure, admixture history and local adaptation in Peninsular Malaysia - Lian Deng; Boon Peng Hoh; Dongsheng Lu; Ruiqing Fu; Maude E. Phipps; Shilin Li; Ab Rajab Nur-Shafawati; Wan Isa Hatin; Endom Ismail; Siti Shuhada Mokhtar; Li Jin; Bin Alwi Zilfalil; et al. (Human Genetics, 2014)

Intraperitoneal delivery of paclitaxel by poly(ether-anhydride) microspheres effectively suppresses tumor growth in a murine metastatic ovarian cancer model - Ming Yang; Tao Yu; Joseph Wood; Ying-Ying Wang; Benjamin C. Tang; Qi Zeng; Brian W. Simons; Jie Fu; Chi-Mu Chuang; Samuel K. Lai; T.-C. Wu; Chien-Fu Hung; et al. (Drug Delivery and Translational Research, 2014)

Genetic diversity analysis of yellow mustard (Sinapis alba L.) germplasm based on genotyping by sequencing - Yong-Bi Fu; Bifang Cheng; Gregory W. Peterson (Genetic Resources and Crop Evolution, 2014)

The Development of Dentotropic Micelles with Biodegradable Tooth-Binding Moieties - Fu Chen; Zhenshan Jia; Kelly C. Rice; Richard A. Reinhardt; Kenneth W. Bayles; Dong Wang (Pharmaceutical Research, 2013)

Tai Chi practitioners have better postural control and selective attention in stepping down with and without a concurrent auditory response task - Xi Lu; Ka-Chun Siu; Siu N. Fu; Christina W. Y. Hui-Chan; William W. N. Tsang (European Journal of Applied Physiology, 2013)

Global transcriptome analysis and identification of a CONSTANS-like gene family in the orchid Erycina pusilla - Ming-Lun Chou; Ming-Che Shih; Ming-Tsair Chan; Shih-Yi Liao; Chen-Tran Hsu; Yao-Ting Haung; Jeremy J. W. Chen; Der-Chih Liao; Fu-Hui Wu; Choun-Sea Lin (Planta, 2013)

Scanning Electron Microscopy Studies of the Antennal Sensilla of Metaphycus parasaissetiae Zhang & Huang (Hymenoptera: Encyrtidae) - H Zhou; W J Wu; F P Zhang; Y G Fu (Neotropical Entomology, 2013)

Catalog of Erycina pusilla miRNA and categorization of reproductive phase-related miRNAs and their target gene families - Choun-Sea Lin; Jeremy J. W. Chen; Yao-Ting Huang; Chen-Tran Hsu; Hsiang-Chia Lu; Ming-Lun Chou; Li-Chi Chen; Chia-I Ou; Der-Chih Liao; Ysuan-Yu Yeh; Song-Bing Chang; Su-Chen Shen; et al. (Plant Molecular Biology, 2013)

Scl gene construction, expression and effect on hemangioma - H. X. Yin; Z. H. Zhang; J. C. Shen; A. L. Zhang; T. Y. Zhang; J. X. Luo; C. Y. Fu; X. P. Yi; Z. W. Liu; S. S. Yang; B. Zhou; X. Fu (Molecular Biology Reports, 2013)

River islands, refugia and genetic structuring in the endemic brown frog R ana kukunoris ( A nura, R anidae) of the Q inghai‐ T ibetan P lateau - Weiwei Zhou; Fang Yan; Jinzhong Fu; Shifang Wu; Robert W. Murphy; Jing Che; Yaping Zhang (Molecular Ecology, 2013)
Frequently, P leistocene climatic cycling has been found to be the diver of genetic structuring in populations, even in areas that did not have continental ice sheets, such as on the Q inghai‐ T ibetan P lateau ( QTP ). Typically, species distributed on the plateau have been hypothesized to re‐treat to south‐eastern refugia, especially during the L ast G lacial M aximum ( LGM ). We evaluated sequence variation in the mitochondrial DNA gene Cytb and the nuclear DNA gene RAG ‐1 in R ana kukunoris , a species endemic to the QTP . Two major lineages, N and S, were identified, and lineage N was further subdivided into N 1 and N 2. The geographical distribution and genealogical divergences supported the hypothesis of multiple refugia. However, major lineages and sublineages diverged prior to the LGM . Demographical expansion was detected only in lineage S and sublineage N 2. Sublineage N 1 might have survived several glacial cycles in situ and did not expand after the LGM because of the absence of suitable habitat; it survived in river islands. Genetic analysis and environment modelling suggested that the north‐eastern edge of QTP contained a major refugium for R . kukunoris . From here, lineage S dispersed southwards after the LGM . Two microrefugia in northern Q ilian M ountains greatly contributed to current level of intraspecific genetic diversity. These results were found to have important implications for the habitat conservation in N orthwest C hina.

Arsenic accumulation and distribution in the tissues of inbred lines in maize (Zea mays L.) - Z. H. Liu; W. H. Li; H. Y. Qi; G. L. Song; D. Ding; Z. Y. Fu; J. B. Liu; J. H. Tang (Genetic Resources and Crop Evolution, 2012)

An enormous Jurassic turtle bone bed from the Turpan Basin of Xinjiang, China - Oliver Wings; Márton Rabi; Jörg W. Schneider; Leonie Schwermann; Ge Sun; Chang-Fu Zhou; Walter G. Joyce (The Science of Nature, 2012)

Prevention of Orthopedic Device-Associated Osteomyelitis Using Oxacillin-Containing Biomineral-Binding Liposomes - Xin-Ming Liu; Yijia Zhang; Fu Chen; Irine Khutsishvili; Edward V. Fehringer; Luis A. Marky; Kenneth W. Bayles; Dong Wang (Pharmaceutical Research, 2012)

Microbiologic characteristics of pathogenic bacteria from hospitalized trauma patients who survived Wenchuan earthquake - B. Zhang; Z. Liu; Z. Lin; X. Zhang; W. Fu (European Journal of Clinical Microbiology & Infectious Diseases, 2012)

A 20-year reanalysis experiment in the Baltic Sea using three-dimensional variational (3DVAR) method - W. Fu; J. She; M. Dobrynin (Ocean Science, 2012)
A 20-year retrospective reanalysis of the ocean state in the Baltic Sea is constructed by assimilating available historical temperature and salinity profiles into an operational numerical model with three-dimensional variational (3DVAR) method. To determine the accuracy of the reanalysis, the authors present a series of comparisons to independent observations on a monthly mean basis. In the reanalysis, temperature (T) and salinity (S) fit better with independent measurements than the free run at different depths. Overall, the mean biases of temperature and salinity for the 20 year period are reduced by 0.32 °C and 0.34 psu, respectively. Similarly, the mean root mean square error (RMSE) is decreased by 0.35 °C for temperature and 0.3 psu for salinity compared to the free run. The modeled sea surface temperature, which is mainly controlled by the weather forcing, shows the least improvements due to sparse in situ observations. Deep layers, on the other hand, witness significant and stable model error improvements. In particular, the salinity related to saline water intrusions into the Baltic Proper is largely improved in the reanalysis. The major inflow events such as in 1993 and 2003 are captured more accurately as the model salinity in the bottom layer is increased by 2–3 psu. Compared to independent sea level at 14 tide gauge stations, the correlation between model and observation is increased by 2%–5%, while the RMSE is generally reduced by 10 cm. It is found that the reduction of RMSE comes mainly from the reduction of mean bias. In addition, the changes in density induced by the assimilation of T/S contribute little to the barotropic transport in the shallow Danish Transition zone. The mixed layer depth exhibits strong seasonal variations in the Baltic Sea. The basin-averaged value is about 10 m in summer and 30 m in winter. By comparison, the assimilation induces a change of 20 m to the mixed layer depth in deep waters and wintertime, whereas small changes of about 2 m occur in summer and shallow waters. It is related to the strong heating in summer and the dominant role of the surface forcing in shallow water, which largely offset the effect of the assimilation.

Effects of Tai Chi on pre-landing muscle response latency during stepping down while performing a concurrent mental task in older adults - William W. N. Tsang; Christina W. Y. Hui-Chan; Siu N. Fu (European Journal of Applied Physiology, 2012)

Constitutive expression of barley α-amylase in Pichia pastoris by high-density cell culture - Z. W. Liu; H. X. Yin; X. P. Yi; A. L. Zhang; J. X. Luo; T. Y. Zhang; C. Y. Fu; Z. H. Zhang; J. C. Shen; L. P. Chen (Molecular Biology Reports, 2012)

Balance control in very old adults with and without visual impairment - Ellen W. Chen; Amy S. N. Fu; K. M. Chan; William W. N. Tsang (European Journal of Applied Physiology, 2012)

d-amino acids for the enhancement of a binary biocide cocktail consisting of THPS and EDDS against an SRB biofilm - D. Xu; J. Wen; W. Fu; T. Gu; I. Raad (World Journal of Microbiology and Biotechnology, 2012)

Heterotrophic bacterial and Synechococcus spp. Growth and mortality along the inshore-offshore in the East China Sea in summer - An-Yi Tsai; Gwo-Ching Gong; Robert W. Sanders; Kuo-Ping Chiang; Chien-Fu Chao (Journal of Oceanography, 2012)

In Vitro and In Vivo Investigation of Drug-Eluting Implants for the Treatment of Periodontal Disease - Fu-Ying Lee; Dave W. Chen; Chih-Chien Hu; Yu-Te Hsieh; Shih-Jung Liu; Err-Cheng Chan (AAPS PharmSciTech, 2011)

A pre-operational three Dimensional variational data assimilation system in the North/Baltic Sea - S. Y. Zhuang; W. W. Fu; J. She (Ocean Science, 2011)
This paper describes the implementation and evaluation of a pre-operational three dimensional variational (3DVAR) data assimilation system for the North/Baltic Sea. Univariate analysis for both temperature and salinity is applied in a 3DVAR scheme in which the horizontal component of the background error covariance is modeled by an isotropic recursive filter (IRF) and the vertical component is represented by dominant Empirical Orthogonal Functions (EOFs). Observations of temperature and salinity (T/S) profiles in the North/Baltic Sea are assimilated in the year of 2005. Effect of the 3DVAR scheme is assessed by a comparison between data assimilation run and control run. The statistical analysis indicates that the model simulation is significantly improved with the 3DVAR scheme. On average, the root mean square errors (RMSE) of temperature and salinity are reduced by 0.2 °C and 0.25 psu in the North/Baltic Sea. In addition, the bias of temperature and salinity is also decreased by 0.1 °C and 0.2 psu, respectively. Starting from an analyzed initial state, one month simulation without assimilation is carried out with the aim of examining the persistence of the initial impact. It is shown that the assimilated initial state can impact the model simulation for nearly two weeks. The influence on salinity is more pronounced than temperature.

Portal protein diversity and phage ecology - Matthew B. Sullivan; Maureen L. Coleman; Vanessa Quinlivan; Jessica E. Rosenkrantz; Alicia S. DeFrancesco; G. Tan; Ross Fu; Jessica A. Lee; John B. Waterbury; Joseph P. Bielawski; Sallie W. Chisholm (Environmental Microbiology, 2011)

Low-level Taekwondo practitioners have better somatosensory organisation in standing balance than sedentary people - Hio-Teng Leong; Siu N. Fu; Gabriel Y. F. Ng; William W. N. Tsang (European Journal of Applied Physiology, 2011)

Early-life stress and cognitive outcome - Dawson W. Hedges; Fu Lye Woon (Psychopharmacology, 2011)

Assessment of the three dimensional temperature and salinity observational networks in the Baltic Sea and North Sea - W. Fu; J. L. Høyer; J. She (Ocean Science, 2011)
The spatial averaged correlations are presented in 1.5° × 1.5° bins for the North and Baltic Sea region. The averaged correlations are computed based on the proxy ocean data generated by the operational forecast model of Danish Meteorology Institute (DMI). It is shown that the spatial distribution of the averaged correlations could reflect the overall influence of the local atmospheric forcing, complex topography, coastlines, boundary and bottom effect, etc. Comparisons with the satellite SST data demonstrate that the proxy ocean data reproduce realistic results at the surface. Based on the spatial bin-averaged correlations, a general correlation model is assumed to approximate the spatial and temporal correlation structure. Parameters of the correlation model are obtained on the standard Levitus levels. It is found that the correlation model is not the typical Guaussian-type function. For instance, the exponents of the correlation model vary in the longitudinal direction from 0.75 at the surface to 1.33 at the depth of 250 m for temperature. For salinity, the temporal correlation can be approximated with an exponential function. Two complementary quality-indicators, effective coverage rate and "explained" variance, are defined based on the correlation models obtained above. The two indicators are able to identify the "influence area" of the information content in a given observation network and the relative importance of observations at different locations. By these indicators, the 3-D temperature and salinity observational networks are assessed in the Baltic Sea and North Sea for the period 2004–2006. It is found that the surface level is more effectively covered than the deep waters with existing networks. In addition, the Belt Sea and the Baltic Proper also show good coverage for both temperature and salinity. However, more observations are required in the Norwegian Trench and Kattegat. In the vertical, the two indicators show smaller values from 50 m to 125 m in this region, indicating the need for more observations.

Stability Kinetics of Influenza Vaccine Coated onto Microneedles During Drying and Storage - Yeu-Chun Kim; Fu-Shi Quan; Richard W. Compans; Sang-Moo Kang; Mark R. Prausnitz (Pharmaceutical Research, 2011)

Microbial dynamics in an oligotrophic bay of the western subtropical Pacific: Impact of short-term heavy freshwater runoff and upwelling - An-Yi Tsai; Gwo-Ching Gong; Robert W. Sanders; Chien-Fu Chao; Kuo-Ping Chiang (Journal of Oceanography, 2010)

Triclosan-Loaded Tooth-Binding Micelles for Prevention and Treatment of Dental Biofilm - Fu Chen; Kelly C. Rice; Xin-Ming Liu; Richard A. Reinhardt; Kenneth W. Bayles; Dong Wang (Pharmaceutical Research, 2010)

Genomic analysis of oceanic cyanobacterial myoviruses compared with T4‐like myoviruses from diverse hosts and environments - Matthew B. Sullivan; Katherine H. Huang; Julio C. Ignacio‐Espinoza; Aaron M. Berlin; Libusha Kelly; Peter R. Weigele; Alicia S. DeFrancesco; Suzanne E. Kern; Luke R. Thompson; Sarah Young; Chandri Yandava; Ross Fu; et al. (Environmental Microbiology, 2010)
Summary T4‐like myoviruses are ubiquitous, and their genes are among the most abundant documented in ocean systems. Here we compare 26 T4‐like genomes, including 10 from non‐cyanobacterial myoviruses, and 16 from marine cyanobacterial myoviruses (cyanophages) isolated on diverse Prochlorococcus or Synechococcus hosts. A core genome of 38 virion construction and DNA replication genes was observed in all 26 genomes, with 32 and 25 additional genes shared among the non‐cyanophage and cyanophage subsets, respectively. These hierarchical cores are highly syntenic across the genomes, and sampled to saturation. The 25 cyanophage core genes include six previously described genes with putative functions ( psbA , mazG , phoH , hsp20 , hli03 , cobS ), a hypothetical protein with a potential phytanoyl‐CoA dioxygenase domain, two virion structural genes, and 16 hypothetical genes. Beyond previously described cyanophage‐encoded photosynthesis and phosphate stress genes, we observed core genes that may play a role in nitrogen metabolism during infection through modulation of 2‐oxoglutarate. Patterns among non‐core genes that may drive niche diversification revealed that phosphorus‐related gene content reflects source waters rather than host strain used for isolation, and that carbon metabolism genes appear associated with putative mobile elements. As well, phages isolated on Synechococcus had higher genome‐wide %G+C and often contained different gene subsets (e.g. petE , zwf , gnd , prnA , cpeT ) than those isolated on Prochlorococcus . However, no clear diagnostic genes emerged to distinguish these phage groups, suggesting blurred boundaries possibly due to cross‐infection. Finally, genome‐wide comparisons of both diverse and closely related, co‐isolated genomes provide a locus‐to‐locus variability metric that will prove valuable for interpreting metagenomic data sets.

Molecular characterization and association analysis of FBXO40 with partial hematological indexes in pig - Z. W. Wang; X. Y. Li; Z. L. Tang; S. L. Yang; Z. Z. Ying; T. Fu; B. Fan; Y. L. Mu; H. Ao; K. Li (Molecular Biology Reports, 2010)

Genetic diversity of cultivated flax (Linum usitatissimum L.) and its wild progenitor pale flax (Linum bienne Mill.) as revealed by ISSR markers - Hüseyin Uysal; Yong-Bi Fu; Orhan Kurt; Gregory W. Peterson; Axel Diederichsen; Peter Kusters (Genetic Resources and Crop Evolution, 2010)

OSTM/Jason-2: Assessment of the System Performances (Ocean Surface Topography Mission: OSTM) - G. Zaouche; J. Perbos; T. Lafon; V. Couderc; J. Lambin; J. D. Desjonqueres; C. Jayles; E. Jurado; P. Vaze; L.-L. Fu; S. Brown; F. Parisot; et al. (Marine Geodesy, 2010)

Formulation of Microneedles Coated with Influenza Virus-like Particle Vaccine - Yeu-Chun Kim; Fu-Shi Quan; Richard W. Compans; Sang-Moo Kang; Mark R. Prausnitz (AAPS PharmSciTech, 2010)

Population-based resequencing analysis of improved wheat germplasm at wheat leaf rust resistance locus Lr21 - Yong-Bi Fu; Gregory W. Peterson; Brent D. McCallum; Li Huang (Theoretical and Applied Genetics, 2010)

Multiple origins of zircons in jadeitite - Bin Fu; John W. Valley; Noriko T. Kita; Michael J. Spicuzza; Chad Paton; Tatsuki Tsujimori; Michael Bröcker; George E. Harlow (Contributions to Mineralogy and Petrology, 2010)

Mapping of QTLs detected in a Brassica napus DH population for resistance to Sclerotinia sclerotiorum in multiple environments - Xiangrui Yin; Bin Yi; Wei Chen; Weijie Zhang; Jinxing Tu; W. G. Dilantha Fernando; Tingdong Fu (Euphytica, 2010)

Environmental control of open‐ocean phytoplankton groups: Now and in the future - Philip W. Boyd; Robert Strzepek; Feixue Fu; David A. Hutchins (Limnology and Oceanography, 2010)
Climate change will alter concurrently many environmental factors that exert control over oceanic phytoplankton. Recent laboratory culture work, shipboard experiments, and field surveys reveal many remaining unknowns about the bottom‐up controls for five globally important algal groups. Increasing uncertainties exist, respectively, for picocyanobacteria, diatoms, Phaeocystis spp., N 2 ‐fixing cyanobacteria, and coccolithophores. This missing information about current environmental controls will hinder progress in modeling how these phytoplankton will be influenced by climate change. A review of conceptual approaches used to elucidate the relationship between environmental controls and phytoplankton dominance, from Margalef's mandala to functional traits, uncovered limitations regarding their application to climate‐change scenarios. For example, these previous approaches have insufficient scope or dimensions to take into account the confounding effects of synergistic and antagonistic interactions of multiple environmental change variables. A new approach is needed that considers all of the different environmental properties altered by climate change and their interactions while at the same time permitting a subset of the most significant controls for a specific phytoplankton group to be isolated and evaluated in factorial matrix perturbation experiments. We advocate three new interlinked approaches, including environmental clusters that incorporate all factors (temperature, CO 2 , light, nutrients, and trace metals), which both exert control over present‐day floristics and will be altered by climate change. By carefully linking a holistic conceptual approach to a reductionist experimental design, the future responses of open‐ocean phytoplankton groups to a complex, rapidly changing environment can be better predicted.

Epigenetic regulation of peanut allergen gene Ara h 3 in developing embryos - Guohua Fu; Yujuan Zhong; Chenlong Li; Yin Li; Xiaodong Lin; Bin Liao; Edward W. T. Tsang; Keqiang Wu; Shangzhi Huang (Planta, 2010)

Impacts of cascade run-of-river dams on benthic diatoms in the Xiangxi River, China - N. Wu; T. Tang; X. Fu; W. Jiang; F. Li; S. Zhou; Q. Cai; N. Fohrer (Aquatic Sciences, 2010)

P2X7 receptor expression is decreased in epithelial cancer cells of ectodermal, uro-genital sinus, and distal paramesonephric duct origin - Xin Li; Xiaoping Qi; Lingyin Zhou; Wen Fu; Fadi W. Abdul-Karim; Gregory MacLennan; George I. Gorodeski (Purinergic Signalling, 2009)

Differential expression of candidate genes for lignin biosynthesis under drought stress in maize leaves - Y. Hu; W. Ch. Li; Y. Q. Xu; G. J. Li; Y. Liao; F. -L. Fu (Journal of Applied Genetics, 2009)

Development and characterization of new microsatellite loci from Chinese mitten crab (Eriocheir sinensis) - Rui X. Mao; Ying Y. Zhao; Fu J. Liu; Zhi Y. Jia; Ning Hou; Yu M. Chang; Cui Y. Lu; Li Q. Liang; Xiao W. Sun (Conservation Genetics, 2009)

Phylogeographical analysis of an estuarine fish, Salanx ariakensis (Osmeridae: Salanginae) in the north‐western Pacific - X. Hua; W. Wang; W. Yin; Q. He; B. Jin; J. Li; J. Chen; C. Fu (Journal of Fish Biology, 2009)
This study extended the geographic coverage of a previous study to explore population genetic structure and demographic history in the Ariake icefish Salanx ariakensis from three populations of continental coastlines and one island population in the north‐western Pacific based on a partial sequence of the mitochondrial cytochrome b gene. The S. ariakensis showed high genetic diversity and strong genetic structure. Phylogenetic analysis showed a shallow gene tree with no clear phylogeographical structure. Contiguous range expansion and restricted gene flow were inferred to be main population events by nested‐clade analysis. Significant genetic differentiations between populations could be attributable to negligible gene flow by coalescent analysis. High nucleotide diversity of each population was due to geographic mixing of heterogenous haplotypes during lowering sea levels of the Pleistocene. These findings indicate that cycles of geographic isolation and secondary contact happened in the Pleistocene glacial–interglacial cycles shaping genetic structure and population demography of S. ariakensis .

Advance and prospectus of seasonal prediction: assessment of the APCC/CliPAS 14-model ensemble retrospective seasonal prediction (1980–2004) - Bin Wang; June-Yi Lee; In-Sik Kang; J. Shukla; C.-K. Park; A. Kumar; J. Schemm; S. Cocke; J.-S. Kug; J.-J. Luo; T. Zhou; B. Wang; et al. (Climate Dynamics, 2009)

Caspase-3 binds diverse P4 residues in peptides as revealed by crystallography and structural modeling - Bin Fang; Guoxing Fu; Johnson Agniswamy; Robert W. Harrison; Irene T. Weber (Apoptosis, 2009)

Lipid rafts play an important role in the vesicular stomatitis virus life cycle - W. Wang; Y. J. Fu; Y. G. Zu; N. Wu; J. Reichling; T. Efferth (Archives of Virology, 2009)

Genetic Diversity of Canadian and Exotic Potato Germplasm Revealed by Simple Sequence Repeat Markers - Yong-Bi Fu; Gregory W. Peterson; Ken W. Richards; T. Richard Tarn; Jane E. Percy (American Journal of Potato Research, 2009)

Reduced swimming abilities in fast‐growing transgenic common carp Cyprinus carpio associated with their morphological variations - D. Li; W. Hu; Y. Wang; Z. Zhu; C. Fu (Journal of Fish Biology, 2009)
Critical swimming speeds ( U crit ) and morphological characters were compared between the F 4 generation of GH‐transgenic common carp Cyprinus carpio and the non‐transgenic controls. Transgenic fish displayed a mean absolute U crit value 22·3% lower than the controls. Principal component analysis identified variations in body shape, with transgenic fish having significantly deeper head, longer caudal length of the dorsal region, longer standard length ( L S ) and shallower body and caudal region, and shorter caudal length of the ventral region. Swimming speeds were related to the combination of deeper body and caudal region, longer caudal length of the ventral region, shallower head depth, shorter caudal length of dorsal region and L S . These findings suggest that morphological variations which are poorly suited to produce maximum thrust and minimum drag in GH‐transgenic C. carpio may be responsible for their lower swimming abilities in comparison with non‐transgenic controls.

Predictability of South American low‐level jet using QuikSCAT ocean surface wind - H. Wang; R. Fu; J. K. Schemm; W. Tang; W. T. Liu (International Journal of Remote Sensing, 2008)

Structural basis for executioner caspase recognition of P5 position in substrates - Guoxing Fu; Alexander A. Chumanevich; Johnson Agniswamy; Bin Fang; Robert W. Harrison; Irene T. Weber (Apoptosis, 2008)

Interactions between changing pCO2, N2 fixation, and Fe limitation in the marine unicellular cyanobacterium Crocosphaera - Fei-Xue Fu; Margaret R. Mulholland; Nathan S. Garcia; Aaron Beck; Peter W. Bernhardt; Mark E. Warner; Sergio A. Sañudo-Wilhelmy; David A. Hutchins (Limnology and Oceanography, 2008)
We examined the physiological responses of steady‐state iron (Fe)‐replete and Fe‐limited cultures of the biogeochemically critical marine unicellular diazotrophic cyanobacterium Crocosphaera at glacial (19 Pa; 190 ppm), current (39 Pa; 380 ppm), and projected year 2100 (76 Pa; 750 ppm) CO 2 levels. Rates of N 2 and CO 2 fixation and growth increased in step with increasing partial pressure of CO 2 (pCO 2 ), but only under Fe‐replete conditions. N 2 and carbon fixation rates at 75 Pa CO 2 were 1.4‐1.8‐fold and 1.2‐2.0‐fold higher, respectively, relative to those at present day and glacial pCO 2 levels. In Fe‐replete cultures, cellular Fe and molybdenum quotas varied threefold and were linearly related to N 2 fixation rates and to external pCO 2 . However, N 2 fixation and trace metal quotas were decoupled from pCO 2 in Fe‐limited Crocosphaera . Higher CO 2 and Fe concentrations both resulted in increased cellular pigment contents and affected photosynthesis vs. irradiance parameters. If these results also apply to natural Crocosphaera populations, anthropogenic CO 2 enrichment could substantially increase global oceanic N 2 and CO 2 fixation, but this effect may be tempered by Fe availability. Possible biogeochemical consequences may include elevated inputs of new nitrogen to the ocean and increased potential for Fe and/or phosphorus limitation in the future high‐CO 2 ocean, and feedbacks to atmospheric pCO 2 in both the near future and over glacial to interglacial timescales.

Portal protein diversity and phage ecology - Matthew B. Sullivan; Maureen L. Coleman; Vanessa Quinlivan; Jessica E. Rosenkrantz; Alicia S. DeFrancesco; G. Tan; Ross Fu; Jessica A. Lee; John B. Waterbury; Joseph P. Bielawski; Sallie W. Chisholm (Environmental Microbiology, 2008)
Summary Oceanic phages are critical components of the global ecosystem, where they play a role in microbial mortality and evolution. Our understanding of phage diversity is greatly limited by the lack of useful genetic diversity measures. Previous studies, focusing on myophages that infect the marine cyanobacterium Synechococcus , have used the coliphage T4 portal‐protein‐encoding homologue, gene 20 ( g20 ), as a diversity marker. These studies revealed 10 sequence clusters, 9 oceanic and 1 freshwater, where only 3 contained cultured representatives. We sequenced g20 from 38 marine myophages isolated using a diversity of Synechococcus and Prochlorococcus hosts to see if any would fall into the clusters that lacked cultured representatives. On the contrary, all fell into the three clusters that already contained sequences from cultured phages. Further, there was no obvious relationship between host of isolation, or host range, and g20 sequence similarity. We next expanded our analyses to all available g20 sequences (769 sequences), which include PCR amplicons from wild uncultured phages, non‐PCR amplified sequences identified in the Global Ocean Survey (GOS) metagenomic database, as well as sequences from cultured phages, to evaluate the relationship between g20 sequence clusters and habitat features from which the phage sequences were isolated. Even in this meta‐data set, very few sequences fell into the sequence clusters without cultured representatives, suggesting that the latter are very rare, or sequencing artefacts. In contrast, sequences most similar to the culture‐containing clusters, the freshwater cluster and two novel clusters, were more highly represented, with one particular culture‐containing cluster representing the dominant g20 genotype in the unamplified GOS sequence data. Finally, while some g20 sequences were non‐randomly distributed with respect to habitat, there were always numerous exceptions to general patterns, indicating that phage portal proteins are not good predictors of a phage's host or the habitat in which a particular phage may thrive.

Importance of Small Pores in Microcrystalline Cellulose for Controlling Water Distribution during Extrusion–Spheronization - Josephine L. P. Soh; Lei Yang; Celine V. Liew; Fu D. Cui; Paul W. S. Heng (AAPS PharmSciTech, 2008)

Simulation of direct effects of black carbon aerosol on temperature and hydrological cycle in Asia by a Regional Climate Model - J. Wu; C. Fu; Y. Xu; J. P. Tang; W. Wang; Z. Wang (Meteorology and Atmospheric Physics, 2008)

Ti-in-zircon thermometry: applications and limitations - Bin Fu; F. Zeb Page; Aaron J. Cavosie; John Fournelle; Noriko T. Kita; Jade Star Lackey; Simon A. Wilde; John W. Valley (Contributions to Mineralogy and Petrology, 2008)

Response of Brassica napus and B. juncea germplasm from Australia, China and India to Australian populations of Leptosphaeria maculans - C. X. Li; N. Wratten; P. A. Salisbury; W. A. Burton; T. D. Potter; G. Walton; Hua Li; K. Sivasithamparam; Surinder S. Banga; Shashi Banga; D. Singh; S. Y. Liu; et al. (Australasian Plant Pathology, 2008)

Fast‐growing transgenic common carp mounting compensatory growth - C. Fu; D. Li; W. Hu; Y. Wang; Z. Zhu (Journal of Fish Biology, 2007)
Compensatory growth is a phase of accelerated growth apparent when favourable conditions are restored after a period of growth depression. To investigate if F 2 common ‘all‐fish’ growth hormone gene transgenic common carp ( Cyprinus carpio ) could mount compensatory growth, a 9 week study at 29° C was performed. The control group was fed to satiation twice a day throughout the experiment. The other two groups were deprived of feed for 1 or 2 weeks, respectively, and then fed to satiation during the re‐feeding period. At the end of the experiment, the live masses of fish in the deprived groups were still significantly lower than those of the controls. During the re‐feeding period, size‐adjusted mean specific growth rates and mean feed intakes were significantly higher in the deprived fish than in the controls, indicating a partial compensatory growth response in these fish. No significant differences were found in food conversion efficiency between the deprived and control fish during re‐feeding, suggesting that hyperphagia was the mechanism responsible for increased growth rates. The proximate composition of the deprived fish at the end of the experiment was similar to that of the control fish. This study is, to our knowledge, the first to report that fast‐growing transgenic fish can achieve partial compensation of growth following starvation.

Two new flavanes and bioactive compounds from Daphne tangutica Maxim - W. Zhang; Y. H. Shen; Z. Y. Lou; R. H. Liu; C. Zhang; P. Fu; L. Shan; W. D. Zhang (Natural Product Research, 2007)

Poster abstracts - J. Ferrie; M. Shipley; F. Cappuccio; E. Brunner; M. Miller; M. Kumari; M. Marmot; A. Coenen; J. L. Castillo; F. Araya; G. Bustamante; L. Montecino; et al. (Sleep and Biological Rhythms, 2007)

Relative Contributions of Collagen and Elastin to Elasticity of the Vocal Fold Under Tension - Roger W. Chan; Min Fu; Lindsay Young; Neeraj Tirunagari (Annals of Biomedical Engineering, 2007)

CO 2 control of Trichodesmium N 2 fixation, photosynthesis, growth rates, and elemental ratios: Implications for past, present, and future ocean biogeochemistry - D. A. Hutchins; F.-X. Fu; Y. Zhang; M. E. Warner; Y. Feng; K. Portune; P. W. Bernhardt; M. R. Mulholland (Limnology and Oceanography, 2007)
Diazotrophic marine cyanobacteria in the genus Trichodesmium contribute a large fraction of the new nitrogen entering the oligotrophic oceans, but little is known about how they respond to shifts in global change variables such as carbon dioxide (CO 2 ) and temperature. We compared Trichodesmium dinitrogen (N 2 ) and CO 2 fixation rates during steady‐state growth under past, current, and future CO 2 scenarios, and at two relevant temperatures. At projected CO 2 levels of year 2100 (76 Pa, 750 ppm), N 2 fixation rates of Pacific and Atlantic isolates increased 35–100%, and CO 2 fixation rates increased 15‐128% relative to present day CO 2 conditions (39 Pa, 380 ppm). CO 2 ‐mediated rate increases were of similar relative magnitude in both phosphorus (P)‐replete and P‐limited cultures, suggesting that this effect may be independent of resource limitation. Neither isolate could grow at 15 Pa (150 ppm) CO 2 , but N 2 and CO 2 fixation rates, growth rates, and nitrogen : phosophorus (N : P) ratios all increased significantly between 39 Pa and 152 Pa (1500 ppm). In contrast, these parameters were affected only minimally or not at all by a 4°C temperature change. Photosynthesis versus irradiance parameters, however, responded to both CO 2 and temperature but in different ways for each isolate. These results suggest that by the end of this century, elevated CO 2 could substantially increase global Trichodesmium N 2 and CO 2 fixation, fundamentally altering the current marine N and C cycles and potentially driving some oceanic regimes towards P limitation. CO 2 limitation of Trichodesmium diazotrophy during past glacial periods could also have contributed to setting minimum atmospheric CO 2 levels through downregulation of the biological pump. The relationship between marine N 2 fixation and atmospheric CO 2 concentration appears to be more complex than previously realized and needs to be considered in the context of the rapidly changing oligotrophic oceans.

Growth and energy budget of F 2 ‘all‐fish’ growth hormone gene transgenic common carp - C. Fu; D. Li; W. Hu; Y. Wang; Z. Zhu (Journal of Fish Biology, 2007)
The growth and energy budget for F 2 ‘all‐fish’ growth hormone gene transgenic common carp Cyprinus carpio of two body sizes were investigated at 29·2° C for 21 days. Specific growth rate, feed intake, feed efficiency, digestibility coefficients of dry matter and protein, gross energy intake ( I E ), and the proportion of I E utilized for heat production ( H E ) were significantly higher in the transgenics than in the controls. The proportion of I E directed to waste products [faecal energy ( F E ) and excretory energy loss ( Z E + U E ) where Z E is through the gills and U E through the kidney], and the proportion of metabolizable energy ( M E ) for recovered energy ( R E ) were significantly lower in the transgenics than in the controls. The average energy budget equation of transgenic fish was as follows: 100 I E = 19·3 F E + 6·0 ( Z E + U E ) + 45·2 H E + 29·5 R E or 100 M E = 60·5 H E + 39·5 R E . The average energy budget equation of the controls was: 100 I E = 25·2 F E + 7·4 ( Z E + U E ) + 35·5 H E + 31·9 R E or 100 M E = 52·7 H E + 47·3 R E . These findings indicate that the high growth rate of ‘all‐fish’ transgenic common carp relative to their non‐transgenic counterparts was due to their increased feed intake, reduced lose of waste productions and improved feed efficiency. The benefit of the increased energy intake by transgenic fish, however, was diminished by their increased metabolism.

Two new chemical constituents from Daphne odora Thunb. var. marginata - W. Zhang; W. D. Zhang; R. H. Liu; Y. H. Shen; C. Zhang; H. S. Cheng; P. Fu; L. Shan (Natural Product Research, 2006)

Two new xanthones from Hypericum japonicum - P. Fu; W.-D. Zhang; R. H. Liu; T.-Z. Li; Y.-H. Shen; H.-L. Li; W. Zhang; H.-S. Chen (Natural Product Research, 2006)

Genetic Variation and Relationships of Pedigree-Known Oat, Wheat, and Barley Cultivars Releaved by Bulking and Single-Plant Sampling - Yong-Bi Fu; William G. Legge; John M. Clarke; Ken W. Richards (Genetic Resources and Crop Evolution, 2006)

Successful implantation of intravenously administered stem cells correlates with severity of inflammation in murine myocarditis - Sohail Malek; Emel Kaplan; Ju-Feng Wang; Qingen Ke; Jamal S. Rana; Yu Chen; Bilal G. Rahim; Ma Li; Qin Huang; Yong-Fu Xiao; Freek W. A. Verheugt; James P. Morgan; et al. (Pflügers Archiv - European Journal of Physiology, 2006)

Complete nucleotide sequences and genome characterization of double-stranded RNA 1 and RNA 2 in the Raphanus sativus-root cv. Yipinghong - L. Chen; J. S. Chen; L. Liu; X. Yu; S. Yu; T. Z. Fu; W. H. Liu (Archives of Virology, 2006)

Impact of plant breeding on genetic diversity of the Canadian hard red spring wheat germplasm as revealed by EST-derived SSR markers - Yong-Bi Fu; Gregory W. Peterson; Ju-Kyung Yu; Lifeng Gao; Jizeng Jia; Ken W. Richards (Theoretical and Applied Genetics, 2006)

Seismo-Geochemical Variations in SW Taiwan: Multi-Parameter Automatic Gas Monitoring Results - T. F. Yang; C.-C. Fu; V. Walia; C.-H. Chen; L. L. Chyi; T.-K. Liu; S.-R. Song; M. Lee; C.-W. Lin; C.-C. Lin (Pure and Applied Geophysics, 2006)

Restoration of Marine Coastal Ecosystem Health as a New Goal for Integrated Catchment Management in Tolo Harbor, Hong Kong, China - Fu-Liu Xu; Jun-Yi Hao; Shu Tao; Richard W. Dawson; K. C. Lam; Yongqin David Chen (Environmental Management, 2006)

Trophic modification of essential fatty acids by heterotrophic protists and its effects on the fatty acid composition of the copepod Acartia tonsa - Adriana J. Veloza; Fu-Lin E. Chu; Kam W. Tang (Marine Biology, 2006)

Evidence of the domestication history of flax (Linum usitatissimum L.) from genetic diversity of the sad2 locus - Robin G. Allaby; Gregory W. Peterson; David Andrew Merriwether; Yong-Bi Fu (Theoretical and Applied Genetics, 2005)

Patterns of AFLP variation in a core subset of cultivated hexaploid oat germplasm - Yong Bi Fu; Gregory W. Peterson; David Williams; Ken W. Richards; Jennifer Mitchell Fetch (Theoretical and Applied Genetics, 2005)

Allelic reduction and genetic shift in the Canadian hard red spring wheat germplasm released from 1845 to 2004 - Yong-Bi Fu; Gregory W. Peterson; Ken W. Richards; Daryl Somers; Ron M. DePauw; John M. Clarke (Theoretical and Applied Genetics, 2005)

Intersubgenomic heterosis in seed yield potential observed in a new type of Brassica napus introgressed with partial Brassica rapa genome - W. Qian; X. Chen; D. Fu; J. Zou; J. Meng (Theoretical and Applied Genetics, 2005)

Multiple Flux Rope Events at the High-Latitude Magnetopause: Cluster/Rapid Observation on 26 January, 2001 - Z. Y. Pu; Q. -G. Zong; T. A. Fritz; C. J. Xiao; Z. Y. Huang; S. Y. Fu; Q. Q. Shi; M. W. Dunlop; K. -H. Glassmeier; A. Balogh; P. Daly; H. Reme; et al. (Surveys in Geophysics, 2005)

GISH, AFLP and PCR-RFLP analysis of an intergeneric somatic hybrid combining Goutou sour orange and Poncirus trifoliata - C. H. Fu; C. L. Chen; W. W. Guo; X. X. Deng (Plant Cell Reports, 2004)

Analyses of cis -acting elements that affect the transposition of Mos1 mariner transposons in vivo - D. W. Pledger; Y. Q. Fu; C. J. Coates (Molecular Genetics and Genomics, 2004)

The influence of the land surface on the transition from dry to wet season in Amazonia - R. Fu; W. Li (Theoretical and Applied Climatology, 2004)

Amazonian climate: results and future research - J. H. C. Gash; C. Huntingford; J. A. Marengo; R. A. Betts; P. M. Cox; G. Fisch; R. Fu; A. W. Gandu; P. P. Harris; L. A. T. Machado; C. von Randow; M. A. Silva Dias (Theoretical and Applied Climatology, 2004)

Segmental nerve conduction velocity in vibration-exposed shipyard workers - M. Cherniack; A. J. Brammer; R. Lundstrom; J. Meyer; T. F. Morse; G. Nealy; T. Nilsson; D. Peterson; E. Toppilla; N. Warren; R. W. Fu; H. Bruneau (International Archives of Occupational and Environmental Health, 2004)

Molecular diversity and multilocus organization of the parental lines used in the International Rice Molecular Breeding Program - S. B. Yu; W. J. Xu; C. H. M. Vijayakumar; J. Ali; B. Y. Fu; J. L. Xu; Y. Z. Jiang; R. Marghirang; J. Domingo; C. Aquino; S. S. Virmani; Z. K. Li (Theoretical and Applied Genetics, 2003)

Spontaneous clearance of high-titer serum HBV DNA and risk of hepatocellular carcinoma in a Chinese population - Rebecca A. Harris; Gang Chen; Wen Yao Lin; Fu Min Shen; W. Thomas London; Alison A. Evans (Cancer Causes & Control, 2003)

Insulin 3: From chemical synthesis to biological function - Ping Fu; Ross A. D. Bathgate; Geoffrey W. Tregear; John D. Wade (International Journal of Peptide Research and Therapeutics, 2003)

Assessment of bulking strategies for RAPD analyses of flax germplasm - Yong-Bi Fu; Sarah Guerin; Gregory W. Peterson; John E. Carlson; K.W. Richards (Genetic Resources and Crop Evolution, 2003)

Adult-Plant Resistance to Powdery Mildew in Knox 62 Wheat - J. W. Johnson; Yong-fu Ge; J. J. Roberts; P. Raymer; Yong Seo (Cereal Research Communications, 2003)

Life Cycle assessment of bio-ethanol derived from cellulose - Gloria Zhi Fu; Albert W. Chan; David E. Minns (The International Journal of Life Cycle Assessment, 2003)

Regeneration of citrus sinensis (+) clausena lansium intergeneric triploid and tetraploid somatic hybrids and their identification by molecular markers - C. H. Fu; W. W. Guo; J. H. Liu; X. X. Deng (In Vitro Cellular & Developmental Biology - Plant, 2003)

The distributions and effects of nutrients in the sediments of a shallow eutrophic Chinese lake - Fu-Liu Xu; S. Tao; R. W. Dawson; Z. R. Xu (Hydrobiologia, 2003)

The interfacial mass transfer resistances of the ozone dry deposition over the field soil of Taichung county in Taiwan - Hsin-Min Chang; Len-Fu W. Chang; Fu-Tien Jeng (Environmental Science and Pollution Research, 2002)

Cloning of the promoter for a novel barley gene, Lem1, and its organ-specific promotion of Gfp expression in lemma and palea - Ronald W. Skadsen; Puthigae Sathish; Maria L. Federico; Tillahun Abebe; Jianming Fu; Heidi F. Kaeppler (Plant Molecular Biology, 2002)

Present-day crustal deformation in China relative to ITRF97 kinematic plate model - Y. Fu; W. Zhu; X. Wang; W. Duan; X. Wu; W. Jiao (Journal of Geodesy, 2002)

Distribution of Organochlorine Pesticides in a Sediment Profile of the Pearl River Estuary - X. D. Li; B. X. Mai; G. Zhang; G. Y. Sheng; J. M. Fu; S. M. Pan; O. W. H. Wai; Y. S. Li (Bulletin of Environmental Contamination and Toxicology, 2001)

Distribution of Polycyclic Aromatic Hydrocarbons in Aerosols and Dustfall in Macao - Qi Shihua; Yan Jun; Zhang Gan; Fu Jiamo; Sheng Guoying; Wang Zhishi; S. M. Tong; U. W. Tang; Min Yunshun (Environmental Monitoring and Assessment, 2001)

Attenuated Lapinized Chinese Strain of Classical Swine Fever Virus: Complete Nucleotide Sequence and Character of 3′-Noncoding Region - H. X. Wu; J. F. Wang; C. Y. Zhang; L. Z. Fu; Z. S. Pan; N. Wang; P. W. Zhang; W. G. Zhao (Virus Genes, 2001)

A method for lake ecosystem health assessment: an Ecological Modeling Method (EMM) and its application - Fu-Liu Xu; Richard W. Dawson; Shu Tao; Jun Cao; Ben-Gang Li (Hydrobiologia, 2001)

Erratum: “Short Term In Vivo Precision of Proximal Femoral Finite Element Modeling” (Ann. Biomed. Eng. 28:408–414, 2000) - Dianna D. Cody; Fu J. Hou; George W. Divine; David P. Fyhrie (Annals of Biomedical Engineering, 2000)

Genetic variability among endangered Chinese giant salamanders, Andrias davidianus - Robert W. Murphy; Jinzhong Fu; Darlene E. Upton; Thales De Lema; Er‐Mi Zhao (Molecular Ecology, 2000)
The endangered Chinese giant salamander ( Andrias davidianus ) is endemic to mainland China. Genetic divergence among six populations of the species was investigated by means of isozyme electrophoresis and mitochondrial DNA (mtDNA) sequences. Forty allozyme loci were resolved for all populations; the amount of genetic divergence among populations was comparable to that in other amphibians. mtDNA sequences showed a similar level of divergence. The population from Huangshan is distinct from other populations, indicating the existence of localized divergence. Both allozyme and mtDNA data failed to associate the populations into a pattern corresponding to the three Chinese river systems, which may be the consequence of human relocation. Conservation policies should emphasize the protection of localized populations and cessation of human‐facilitated introductions. Future studies should focus on investigating the divergence among localized populations from isolated mountain regions, particularly using more fine‐grained techniques such as microsatellite DNA.

Oxidative modification of lipoproteins in hypertriglyceridemic patients and hypercholesterolemic rabbits in vivo - Bing W. Liu; Yu Jiang; Ming D. Fu; Yu Liu; Ping Fan (Molecular and Cellular Biochemistry, 2000)

Short Term In Vivo Precision of Proximal Femoral Finite Element Modeling - Dianna D. Cody; Fu J. Hou; George W. Divine; David P. Fyhrie (Annals of Biomedical Engineering, 2000)

Allozyme Variation Patterns and Multiple Hybridization Origins: Clonal Variation Among Four Sibling Parthenogenetic Caucasian Rock Lizards - Jinzhong Fu; Ross D. MacCulloch; Robert W. Murphy; Ilya S. Darevsky; Boris S. Tuniyev (Genetica, 2000)

Visual Evidence of Acidic Environment Within Degrading Poly(lactic-co-glycolic acid) (PLGA) Microspheres - Karen Fu; Daniel W. Pack; Alexander M. Klibanov; Robert Langer (Pharmaceutical Research, 2000)

Limited genetic variation in Lacerta mixta and its parthenogenetic daughter species: evidence from cytochrome b and ATPase 6 gene DNA sequences - Jinzhong Fu; Robert W. Murphy; Ilya S. Darevsky (Genetica, 1999)

Degradation of 3-phenylpropionic acid by Haloferax sp. D1227 - W. Fu; P. Oriel (Extremophiles, 1999)

Gentisate 1,2-dioxygenase from Haloferax sp. D1227 - W. Fu; P. Oriel (Extremophiles, 1998)

Studies on somaclonal variation in Phalaenopsis - W. H. Chen; T. M. Chen; Y. M. Fu; R. M. Hsieh; W. S. Chen (Plant Cell Reports, 1998)

Anchor probes for comparative mapping of grass genera - A. E. Van Deynze; M. E. Sorrells; W. D. Park; N. M. Ayres; H. Fu; S. W. Cartinhour; E. Paul; S. R. McCouch (Theoretical and Applied Genetics, 1998)

Temperature and resistance gene interactions in the expression of resistance to Blumeria Graminis f. sp. Tritici - Yong-fu Ge; W. Johnson; John J. Roberts; S. Rajaram (Euphytica, 1998)

Receptive field properties of visual neurons in the avian nucleus lentiformis mesencephali - Y.-X. Fu; Hong-Feng Gao; M.-W. Guo; S.-R. Wang (Experimental Brain Research, 1998)

Old age, multiple formations or genetic plasticity? Clonal diversity in the uniparental Caucasian rock lizard, Lacerta dahli - Robert W. Murphy; Ilya S. Darevsky; Ross D. MacCulloch; Jinzhong Fu; Larissa A. Kupriyanova; Darlene E. Upton; Felix Danielyan (Genetica, 1997)

Disjunct habitats as islands: genetic variability in the Caucasian rock lizard Lacerta portschinskii - Ross D. MacCulloch; Robert W. Murphy; Jinzhong Fu; Ilya S. Darevsky; Felix Danielyan (Genetica, 1997)

Case 23 nomination of precursory seismic quiescence as a significant precursor - Max Wyss; R. E. Habermann; P. Bodin; Carl Kisslinger; R. O. Burford; F. W. Klein; A. C. Johnson; Zhengxiang Fu (Pure and Applied Geophysics, 1997)

Stereoselective formation of a K-region dihydrodiol from phenanthrene by Streptomyces flavovirens - John B. Sutherland; James P. Freeman; Allison L. Selby; Peter P. Fu; Dwight W. Miller; Carl E. Cerniglia (Archives of Microbiology, 1990)